Porous carbon structure, method for preparing the same, positive electrode material using the same, and battery using the same

By using a high pore volume and self-supported porous carbon structure as the positive electrode material of the air battery, the problem that the positive electrode structure in the prior art cannot fully utilize oxygen is solved, and the size and weight reduction of the air battery and capacity improvement are achieved.

CN113841284BActive Publication Date: 2025-02-07NAT INST FOR MATERIALS SCI
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202080035651.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-03-02
Filing Date
2020-05-21
Publication Date
2025-02-07
Estimated Expiration
2040-05-21

AI Technical Summary

Technical Problem

The positive electrode structure of existing air batteries cannot fully utilize oxygen, resulting in difficulty in reducing the size and weight of the battery, and the capacity improvement potential is not fully utilized.

Method used

A porous carbon structure with high pore volume and self-supporting ability is used as the positive electrode material. The structure is prepared by a specific manufacturing method, including preparing a mixture slurry containing porous carbon particles and a polymer material for bonding, forming, impregnating, Drying and carbonizing treatment form a porous carbon structure with excellent air permeability and ion transport efficiency.

Benefits of technology

The air battery is small in size, light in weight and high discharge capacity, and does not require current collector support, reducing production costs and increasing capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113841284B_ABST
    Figure CN113841284B_ABST
Patent Text Reader

Abstract

The present invention solves the following problems: providing a porous carbon structure having a high micropore volume and being self-sustaining; a method for manufacturing the same; a positive electrode material using the porous carbon structure; and a battery (particularly an air battery) using the porous carbon structure. The present invention is a porous carbon structure, which is used for the positive electrode of an air battery and has voids and a skeleton formed by incorporating carbon, and which satisfies all of the following conditions (a) to (d). (a) The external specific surface area of ​​the t-curve is 300 m 2 / g to 1,600m 2 / g; (b) the total volume of micropores with diameters ranging from 1 nm to 200 nm is within 1.2 cm 3 / g to 7.0cm 3 / g; (c) the total volume of micropores with diameters ranging from 1 nm to 1000 nm is within 2.3 cm 3 / g to 10.0cm 3 / g range; and (d) the total porosity is in the range of 80% to 99%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a porous carbon structure (also referred to as a porous carbon structure), a method for producing the same, a positive electrode material using the porous carbon structure, and a battery using the porous carbon structure.

[0002] The present invention relates to a porous carbon structure and a battery using the porous carbon structure. The porous carbon structure particularly has self-supporting ability, high ion transmission efficiency, high air permeability and wide reaction area, and is suitable for the positive electrode material of a metal-air battery (in this application, the material may also be referred to as "positive electrode material" or "positive electrode structure"). Background Art

[0003] Batteries are gaining attention as a driving force supporting smart society, and the demand for batteries has been growing rapidly. There are various types of batteries, and among them, air batteries are gaining attention due to their small size, light weight, and structure suitable for increasing capacity.

[0004] An air battery is a battery in which oxygen in the air is used as a positive electrode active material and a metal is used as a negative electrode active material. An air battery is also called a metal-air battery and is considered to be a type of fuel cell.

[0005] For example, air batteries are disclosed in Patent Documents 1 and 2, and representative examples of air batteries include lithium-air batteries in which a metal or a compound capable of occluding and releasing lithium ions is used as a negative electrode active material.

[0006] In the air battery, the positive electrode active material is oxygen in the air, and the positive electrode active material can be supplied from the outside of the battery. Therefore, the size and weight of the air battery can be reduced, and it also has a structure suitable for increasing capacity.

[0007] However, currently, the potential of air batteries with respect to size and weight reduction and capacity improvement has not been fully exploited.

[0008] One of the reasons lies in the positive electrode structure.

[0009] As described above, in air batteries, since oxygen in the air serves as the positive electrode active material, the positive electrode structure needs to have a structure that can absorb a large amount of oxygen from the air. In other words, the positive electrode structure needs to have high air or oxygen permeability.

[0010] In addition, the cathode structure needs to have both high ion transport efficiency and a wide reaction field, which are characteristics generally required for batteries.

[0011] Furthermore, in order to reduce the size and weight of air batteries and lower the cost, the cathode structure needs to be self-supporting.

[0012] In this case, carbon is preferred as the material of the positive electrode structure from the viewpoints of easy handling, cost, weight, green environment and recycling. A positive electrode structure made porous to achieve high air or oxygen permeability, that is, a porous carbon structure, is generally used.

[0013] Among porous carbon materials, Ketjen Black (registered trademark) is known to be a material having a large total specific surface area (BET specific surface area), and a material having a large pore volume and specific surface area of ​​so-called mesopores with a pore size of 2 nm or more and 50 nm or less and macropores with a pore size of 50 nm or more. Ketjen Black is used as a raw material for a porous carbon structure used in the positive electrode of an air battery. However, Ketjen Black (registered trademark) is powdery and cannot be self-supporting. For this reason, in order to use Ketjen Black (registered trademark) as a positive electrode structure, the following method must be adopted: a composition containing a binder, etc. is dispersed in a solvent, and the composition is applied to a metal foil, etc. by a doctor blade method, etc., or supported on a metal mesh, etc. Therefore, there is the following problem: the positive electrode structure has a complex structure and has an increased weight, the cost increases, or the flow of air or oxygen is inhibited.

[0014] In conventional air batteries, since the positive electrode still has insufficient characteristics, there is a problem that their original battery characteristics cannot be fully exhibited.

[0015] In view of such problems, Patent Document 1 proposes to use porous carbon as a raw material for a positive electrode layer, wherein the porous carbon includes pores, the pores include mesopores and micropores having a pore size smaller than the pore size of the mesopores, and the carbonaceous walls constituting the outer contour of the mesopores form a three-dimensional network structure, the micropores are formed in the carbonaceous walls, the mesopores are open pores, the pore portions continuously form connected pores, the half width of the pore size distribution of the pores is less than 2nm, the half width of the connected pore size distribution of the connected pores is more than 50nm, and the pore volume of the pores with a pore size of more than 1nm is more than 1.0ml / g and less than 4.0ml / g. In the specification of Patent Document 1, it is described that when forming a positive electrode layer, a method in which a composition containing porous carbon, a binder, etc. is dispersed in a solvent and the composition is applied by a doctor blade method or the like, or a method in which the composition is made by pressure molding, can be used.

[0016] Patent document 2 proposes a lithium-air battery using a positive electrode layer, in which the first pore volume of pores with a pore size of 1 nm or more and 200 nm or less is greater than the second pore volume of pores with a pore size of more than 200 nm and less than 1000 nm. In the specification of patent document 2, a method for forming the positive electrode layer is described, for example, a method of applying a coating obtained by dispersing a composition containing a conductive porous material, a binder, etc. in a solvent to a positive electrode current collector by a doctor blade method or the like, or a method of molding the above composition by pressure molding.

[0017] For example, Non-Patent Documents 1 and 2 disclose Ketjen Black (registered trademark).

[0018] Reference List

[0019] Patent Literature

[0020] Patent document 1: JP 5852548 B

[0021] Patent Document 2: JP 2018-133168 A

[0022] Non-patent literature

[0023] Non-patent document 1: Journal of Printing Science and Technology, Vol. 44, No. 3, pp. 9-19 (2007)

[0024] Non-patent document 2: Tanso, Vol. 222, pp. 140-146 (2006) Summary of the invention

[0025] Technical issues

[0026] An object of the present invention is to provide a battery that is small in size and light in weight and suitable for increasing capacity, in particular, an air battery that is small in size and light in weight and suitable for increasing capacity. To this end, an object of the present invention is to provide a porous carbon structure that has high air or oxygen permeability, high ion transmission efficiency, and a wide reaction field, and the porous carbon structure is suitable as a positive electrode structure of an air battery, in particular, a self-supporting porous carbon structure.

[0027] On the other hand, when the porous carbon described in Patent Document 1 in which the pore volume of pores with a pore size of 1 nm or more is 1.0 ml / g or more and 4.0 ml / g or less is used as the raw material of the positive electrode layer, the pore volume in the positive electrode layer will not become larger than the pore volume in the porous carbon of the raw material. In this case, because a binder is used to form the positive electrode layer, some of the pores of the porous carbon are directly filled with the binder, so the pore volume in the positive electrode layer may become smaller than the pore volume in the porous carbon of the raw material. Therefore, it cannot be said that the required sufficient battery performance is exhibited. Therefore, a positive electrode layer that inherits the pore volume in the porous carbon of the raw material is required, and a positive electrode layer having a large pore volume exceeding the pore volume in the porous carbon as a raw material is further required.

[0028] In addition, in the lithium-air battery using a positive electrode layer described in Patent Document 2 (wherein the first pore volume of pores with a pore size of 1 nm or more and 200 nm or less is greater than the second pore volume of pores with a pore size of greater than 200 nm and less than 10,000 nm), a binder is used to form the positive electrode layer. Therefore, as in the case of Patent Document 1, some of the pores of the porous carbon as a raw material are directly filled with a binder, and the pore volume in the positive electrode layer may become smaller than the pore volume in the porous carbon of the raw material, and the absolute amount of the pore volume in the positive electrode layer is not large. Therefore, it cannot be said that the required sufficient battery performance is exhibited. Therefore, as in the case of Patent Document 1, a positive electrode layer that inherits the pore volume in the porous carbon of the raw material is required, and a positive electrode layer with a large pore volume that exceeds the pore volume in the porous carbon as the raw material is further required. In porous carbon materials, the first pore volume of pores with a pore size of 1 nm or more and 200 nm or less is generally greater than the second pore volume of pores with a pore size of greater than 200 nm and less than 10,000 nm.

[0029] In view of the above situation, an object of the present invention is to provide a porous carbon structure having a high pore volume and being self-supporting, a method for preparing the same, a positive electrode material using the same, and a battery (especially an air battery) using the same.

[0030] Solution to the problem

[0031] In order to solve the above-mentioned problems, the present invention specifically has the following configuration.

[0032] [1] A porous carbon structure for an air battery positive electrode, the porous carbon structure comprising pores and a carbon-containing skeleton and satisfying all of the following conditions (a) to (d):

[0033] (a) t-plot external specific area at 300 m 2 / g or more and 1,600m 2 / g or less;

[0034] (b) The pore volume of pores with a diameter of 1 nm or more and 200 nm or less is 1.2 cm 3 / g or more and 7.0cm 3 / g or less;

[0035] (c) The pore volume of pores with a diameter of 1 nm or more and 1,000 nm or less is 2.3 cm 3 / g or more and 10.0cm 3 / g or less; and

[0036] (d) The total porosity is within a range of 80% to 99%.

[0037] [2] The porous carbon structure according to [1], wherein the porous carbon structure further satisfies the following condition (e):

[0038] (e) The pore volume of pores with a diameter of 200 nm or more and 10,000 nm or less is 2.3 cm 3 / g or more and 8.0cm 3 / g or less.

[0039] [3] The porous carbon structure according to [1] or [2], wherein the pore volume of the pores with a diameter of 1 nm or more and 200 nm or less in (b) is within 2.2 cm 3 / g or more and 7.0cm 3 / g or less.

[0040] [4] The porous carbon structure according to any one of [1] to [3], wherein the pore volume of the pores with a diameter of 1 nm or more and 200 nm or less in (b) is greater than 2.4 cm 3 / g and 6.0cm 3 / g or less.

[0041] [5] The porous carbon structure according to any one of [1] to [4], wherein the pore volume of the pores having a diameter of 1 nm or more and 1,000 nm or less in (c) is within 4.0 cm 3 / g or more and 10.0cm 3 / g or less.

[0042] [6] The porous carbon structure according to [5], wherein the pore volume of the pores with a diameter of 1 nm or more and 1,000 nm or less in (c) is within 4.1 cm 3 / g or more and 9.0cm 3 / g or less.

[0043] [7] The porous carbon structure according to any one of [1] to [6], wherein the apparent density of the porous carbon structure is 0.05 g / cm 3 Above and 0.20g / cm 3 Within the following range.

[0044] [8] The porous carbon structure according to any one of [1] to [7], wherein the total porosity in (d) is in the range of 90% or more and 99% or less.

[0045] [9] The porous carbon structure according to any one of [1] to [8], wherein the skeleton is made of carbon.

[0046]

[10] The porous carbon structure according to any one of [1] to [9], wherein the t-curve external specific surface area in (a) is 900 m 2 / g or more and 1,600m 2 / g or less.

[0047]

[11] The porous carbon structure according to any one of [1] to

[10] , wherein the fluorine content of the porous carbon structure is 0.0002 mass % or less.

[0048]

[12] The porous carbon structure according to any one of [1] to

[11] , which has a self-supporting ability.

[0049]

[13] A method for producing a porous carbon structure according to any one of [1] to

[12] , the method comprising the following steps:

[0050] preparing a mixture slurry containing porous carbon particles and a binding polymer material;

[0051] forming the mixture slurry;

[0052] immersing the sample obtained by the molding step in a solvent in which the bonding polymer material has low solubility;

[0053] drying the sample obtained by the immersion step; and

[0054] The sample obtained through the drying step was subjected to carbonization treatment.

[0055]

[14] The method according to

[13] , wherein the carbonization treatment is performed in an atmosphere of an oxidizing gas or an inert gas.

[0056]

[15] The method according to

[14] , wherein when the carbonization treatment is performed in an atmosphere of an oxidizing gas, an oxygen concentration of the oxidizing gas is in a range of greater than 0.03% and less than 5%.

[0057]

[16] The method according to any one of

[13] to

[15] , wherein the carbonization treatment is performed at a treatment temperature in the range of 350° C. or higher and 3000° C. or lower.

[0058]

[17] The method according to any one of

[13] to

[16] , wherein the carbonization treatment is performed until the pore volume of pores with a diameter of 1 nm or more and 1,000 nm or less in the product obtained by the carbonization treatment reaches 1.02 times or more the pore volume in the porous carbon.

[0059]

[18] The method according to any one of

[13] to

[17] , wherein the mixture slurry further contains carbon fibers.

[0060]

[19] The method according to any one of

[13] to

[18] , further comprising, after the drying step and before the carbonization step, performing an infusibility treatment on the sample obtained by the drying step.

[0061]

[20] According to the method described in any one of

[14] to

[19] , when the carbonization treatment is performed in an oxidizing gas atmosphere, the method further includes, after the carbonization treatment, performing an additional carbonization treatment on the sample obtained by the carbonization treatment under an inert gas atmosphere.

[0062]

[21] A positive electrode material for an air battery, the positive electrode material comprising the porous carbon structure according to any one of [1] to

[12] .

[0063]

[22] An air battery comprising a positive electrode structure, a negative electrode structure, a separator, and an electrolyte member, wherein the positive electrode structure comprises the porous carbon structure according to any one of [1] to

[12] .

[0064]

[23] The air battery according to

[22] , wherein the porous carbon structure has a flow path through which air or oxygen passes.

[0065]

[24] The air battery according to

[22] or

[23] , wherein the positive electrode structure includes a metal-containing positive electrode substrate having a flow path through which air or oxygen passes, and wherein the metal-containing positive electrode substrate is in electrical contact with the porous carbon structure.

[0066]

[25] A porous carbon structure for an air battery positive electrode, the porous carbon structure comprising pores and a carbon-containing skeleton, having self-supporting ability, and satisfying at least one of the following conditions (a) to (e):

[0067] (a) t-curve external specific surface area at 300m 2 / g or more and 1,600m 2 / g or less;

[0068] (b) The pore volume of pores with a diameter of 1 nm or more and 200 nm or less is 1.2 cm 3 / g or more and 7.0cm 3 / g or less;

[0069] (c) The pore volume of pores with a diameter of 1 nm or more and 1,000 nm or less is 2.3 cm 3 / g or more and 10.0cm 3 / g or less;

[0070] (d) a total porosity in the range of 80% or more and 99% or less; and

[0071] (e) The pore volume of pores with a diameter of 200 nm or more and 10,000 nm or less is 2.3 cm 3 / g or more and 8.0cm 3 / g or less.

[0072] Advantageous Effects of the Invention

[0073] According to the present invention, it becomes possible to provide a battery which is small in size and light in weight and suitable for increasing discharge capacity, particularly an air battery which is small in size and light in weight and suitable for increasing capacity.

[0074] An air battery that is small in size and light in weight and suitable for increasing capacity is provided by the porous carbon structure of the present invention, which simultaneously has high air or oxygen permeability, high ion transport efficiency and a wide reaction field, and is self-supporting.

[0075] The porous carbon structure of the present invention has a large number of pores and a skeleton containing carbon, and can meet all of the above conditions (a) to (d). Such a porous carbon structure has an unprecedented high pore volume and is self-supporting. Such a porous carbon structure can be used as a positive electrode material for an air battery. Because such a porous carbon structure itself is self-supporting, when the porous carbon structure is used in a positive electrode structure, a current collector such as a metal mesh is not required, and the size and weight of the air battery can be reduced. In addition, because the porous carbon structure has an unprecedented high pore volume, the porous carbon structure has high air or oxygen permeability, high ion transport efficiency and a large reaction field, so that an air battery with high capacity and high load characteristics can be provided.

[0076] The method for manufacturing the porous carbon structure of the present invention comprises the following steps: preparing a mixture slurry containing porous carbon particles and a bonding polymer material, molding the mixture slurry, impregnating the sample obtained by the molding step in a solvent in which the bonding polymer material has a low solubility, drying the sample obtained by the impregnation step, and carbonizing the sample obtained by the drying step. Therefore, the method can provide the above-mentioned porous carbon structure having a high pore volume and being self-supporting. The carbonization treatment can burn and remove the bonding polymer material, and further burn and remove a portion of the porous carbon particles, so that a bond can be formed between the porous carbon particles. The carbonization treatment can be carried out in an atmosphere of an oxidizing gas or an inert gas. When the carbonization treatment is carried out in an oxidizing gas atmosphere and the oxygen concentration of the oxidizing gas is in a range of greater than 0.03% and less than 5%, the above-mentioned porous carbon structure having a high pore volume and being self-supporting can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0077] Figure 1 is a diagram schematically showing a cross section of a porous carbon structure of the present invention.

[0078] Figure 2 yes Figure 1 Magnified view of part A in FIG.

[0079] Figure 3 yes Figure 2 Magnified view of part B in FIG.

[0080] Figure 4 is a flow chart showing a method for making the porous carbon structure of the present invention.

[0081] Figure 5 is a schematic diagram showing a button battery.

[0082] Figure 6 is a schematic diagram showing another type of button battery.

[0083] Figure 7 is a schematic diagram showing a laminated metal battery (air battery).

[0084] Figure 8 is a SEM image of sample No. 5 of the porous carbon structure (magnification: 5,000).

[0085] Fig. 9 is a high-magnification SEM image of the porous carbon structure No. 5 (magnification: 50,000).

[0086] Fig.10 is a SEM image of the prepared porous carbon structure (sample No. 11 of the porous carbon structure).

[0087] Implementation Description

[0088] Hereinafter, embodiments of the present invention will be described with reference to the accompanying drawings. Similar elements are denoted by similar reference numerals, and description thereof will be omitted. The present invention is not limited to these embodiments.

[0089] In the present invention, a porous carbon structure having a self-supporting ability or being self-supporting refers to a film-like structure that can maintain a shape as a self-supporting film without using a support (in the present application, the structure may also be referred to as a "self-supporting film"). The porous carbon structure is formed of a skeleton mainly containing carbon and is used with a thickness in the range of 20 μm to 800 μm, preferably in the range of 50 μm to 500 μm.

[0090] Specifically, the porous carbon structure (i.e., a self-supporting film) in the sense of the present invention means that in the positive electrode layer, a support is not included, for example, a metal mesh made of a simple metal (such as copper (Cu), tungsten (W), aluminum (Al), nickel (Ni), titanium (Ti), gold (Au), silver (Ag), platinum (Pt), palladium (Pd) or stainless steel (SUS)) or an alloy containing a metal component, and a non-woven fabric or textile composed of components such as carbon fiber and polyester fiber, or means that the positive electrode layer is not formed on a metal foil substrate such as aluminum foil, nickel foil or SUS foil. In addition, the porous carbon structure does not contain an organic binder intended to be adhered to a support or substrate, particularly a fluorine-containing binder. In the porous carbon structure, the fluorine content is less than 0.0002% by mass. The porous carbon structure can be a self-supporting body with practical rigidity and mechanical strength and flexibility.

[0091] <First embodiment>

[0092] In the first embodiment, the porous carbon structure of the present invention will be described.

[0093] Figure 1 is a diagram schematically showing a cross section of the porous carbon structure of the present invention.

[0094] Figure 2 yes Figure 1 Magnified view of part A in FIG.

[0095] Figure 3 yes Figure 2 Magnified view of part B in FIG.

[0096] The porous carbon structure of the present invention has a skeleton 10 containing carbon and a large number of pores 11 and 12. In addition, the porous carbon structure of the present invention satisfies all of the conditions (a) to (d) shown below:

[0097] (a) t-curve external specific surface area at 300m 2 / g or more and 1,600m 2 / g or less;

[0098] (b) The pore volume of pores with a diameter of 1 nm or more and 200 nm or less is 1.2 cm 3 / g or more and 7.0cm 3 / g or less;

[0099] (c) The pore volume of pores with a diameter of 1 nm or more and 1,000 nm or less is 2.3 cm 3 / g or more and 10.0cm 3 / g or less; and

[0100] (d) The total porosity is within a range of 80% to 99%.

[0101] Each of the above conditions (a) to (d) will be described in detail below.

[0102] The "t-curve external specific surface area" in the above condition (a) is determined by an adsorption isotherm diagram obtained by nitrogen adsorption measurement, which plots the layer thickness of the adsorbed nitrogen on the horizontal axis and the amount of the adsorbed nitrogen on the vertical axis. The value obtained by subtracting the t-curve external specific surface area from the specific surface area according to the BET (Brunauer-Emmett-Teller) method (also determined by nitrogen adsorption measurement) is defined as the t-curve micropore specific surface area. The pores represented as t-curve micropores are too small to allow lithium ions and oxygen to enter, and hardly promote the discharge reaction. That is, the t-curve external specific surface area represents the specific surface area of ​​the pores that are effective for the discharge reaction and further the charging reaction. IUPAC describes the definition of pores, and micropores are defined as pores with a pore diameter of less than 2nm, mesopores are defined as pores with a pore diameter of 2nm or more and less than 50nm, and macropores are defined as pores with a pore diameter of 50nm or more.

[0103] In the porous carbon structure of the present invention, the t-curve external specific surface area is within the range of the above condition (a) (i.e., the area is within 300 m 2 / g or more and 1,600m 2 / g or less).

[0104] Because the external specific surface area of ​​the t-curve of the porous carbon structure is 300 m 2 / g or more, thus avoiding the problem that the porous carbon structure has lower air permeability and ion transmission efficiency and the reaction field becomes narrower when used as the positive electrode structure of the battery, which may occur when the external specific surface area of ​​the t-curve is smaller than the above value.

[0105] In addition, because the t-curve external specific surface area of ​​the porous carbon structure is 1,600 m 2 / g or less, so the problem that micropores tend to increase relatively and make it difficult for lithium ions and oxygen to enter is avoided, which may occur when the t-curve external specific surface area is larger than the above value.

[0106] When the lower limit of the external specific surface area of ​​the t-curve is 900m 2 When the surface area of ​​the lithium ion and oxygen is greater than 900 m / g, it is easier to avoid the problem that the discharge capacity may be reduced due to the reduction of the field where lithium ions and oxygen react with each other. Therefore, the lower limit of the external specific surface area of ​​the t-curve is preferably 900 m 2 / g or above.

[0107] The external specific surface area of ​​the t-curve is preferably 900 m 2 / g or more and 1,600m 2 / g or less. When the t-curve external specific surface area is within the above range, when Li ions and oxygen react with each other to produce lithium peroxide during the discharge reaction, there are multiple reaction fields required for oxygen to receive electrons supplied from the positive electrode. This makes more electron transfer possible.

[0108] The above condition (c) "the pore volume of pores with a diameter of 1 nm or more and 1,000 nm or less is within 2.3 cm 3 / g or more and 10.0cm 3 / g or less" (preferably, "the pore volume of pores having a diameter of 1 nm or more and 1,000 nm or less is within a range of 4.0 cm 3 / g or more and 10.0cm 3 / g or less”, and more preferably, “the pore volume of pores having a diameter of 1 nm or more and 1,000 nm or less is within a range of 4.1 cm 3 / g or more and 9.0cm 3 / g or less"), a battery with a high discharge capacity can be provided.

[0109] This makes it possible to transfer more electrons. This is also the case in the charging reaction because there are multiple reaction sites where lithium peroxide transfers electrons to the positive electrode and turns into Li ions and oxygen. This is consistent with the above condition (e) "the pore volume of pores with a diameter of 200 nm or more and 10,000 nm or less is 2.3 cm 3 / g or more and 10.0cm 3 / g or less" (preferably, "the pore volume of pores with a diameter of 200 nm or more and 10,000 nm or less is within a range of 2.3 cm 3 / g or more and 8.0cm 3 / g or less) combined with high-speed charging becomes possible.

[0110] The t-curve external specific surface area is more preferably 930 m 2 / g or more and 1,500m 2 / g or less. Such a value achieves high discharge capacity and high-speed charging. The t-curve external specific surface area is more preferably 950 m 2 / g or more and 1,400m 2 / g or less. Such a value achieves higher discharge capacity and high-speed charging.

[0111] The above condition (b) "the pore volume of pores with a diameter of 1 nm or more and 200 nm or less is within 1.2 cm 3 / g or more and 7.0cm 3 / g or less" means that the pore volume and the number of pores are large, although the pores included in this range have relatively small pore diameters. Pores with a diameter of 1 nm or more and 200 nm or less may correspond to Figure 2 and 3 The pore volume was determined by the BJH method from the adsorption isotherm obtained by nitrogen adsorption measurement.

[0112] When such a porous carbon structure of the present invention is used in a positive electrode of an air battery, more fields are provided for lithium ions and oxygen to react with each other during discharge, and thus a battery exhibiting a high discharge capacity can be provided.

[0113] Because the pore volume of pores with a diameter of 1 nm or more and 200 nm or less is within the range of the above condition (b) (i.e., the pore volume is within 1.2 cm 3 / g or more and 7.0cm 3 / g or less), so the problem that the discharge capacity tends to decrease when the pore volume is less than the above range is avoided, and the problem that the pore volume of pores with a diameter of 200nm or more is relatively reduced, thereby reducing oxygen permeability and diffusivity, and the discharge characteristics at high load (i.e., the discharge capacity at high speed) may be reduced when the pore volume is greater than the above range is avoided. The lower limit of the pore volume is preferably 2.2cm 3 / g or more and more preferably 2.4 cm 3 / g or more, and the upper limit of the pore volume is preferably 7.0 cm 3 / g or less and more preferably 6.0 cm 3 / g or less. Such a value can enable the battery to have a large discharge capacity. Such a value can enable the battery to have an even larger discharge capacity.

[0114] The above condition (c) "the pore volume of pores with a diameter of 1 nm or more and 1,000 nm or less is within 2.3 cm 3 / g or more and 10.0cm 3 / g or less" means that in the porous carbon structure of the present invention, the pore volume of pores with a diameter within the above range is quite large. Pores with a diameter of 1 nm or more and 1,000 nm or less can correspond to Figure 2 and 3 The pore volume was determined by the BJH (Barrett-Joyner-Hallenda) method from the adsorption isotherm obtained by nitrogen adsorption measurement.

[0115] When this porous carbon structure of the present invention is used in the positive electrode (positive electrode structure) of an air battery, more lithium peroxide generated by discharge can be stored, and a battery with high discharge capacity characteristics can be provided. In addition, because the pores within this pore range have a large pore volume, the permeation and diffusion of air or oxygen are facilitated in the porous carbon structure. Therefore, the air or oxygen introduced into the positive electrode from the outside of the battery can diffuse at high speed throughout the carbon particles forming the carbon skeleton. In addition, because the pores within this pore range have a large pore volume, lithium (Li) ions move smoothly, and combined with high air or oxygen permeability and diffusivity, an air battery with excellent high-speed discharge characteristics, i.e., high-load characteristics, can be provided.

[0116] Since the pore volume of pores with a diameter of 1 nm or more and 1,000 nm or less is within the range of the above condition (c) (i.e., the pore volume is within 2.3 cm 3 / g or more and 10.0cm 3 / g or less), so that the problem that the discharge capacity and high-load characteristics tend to decrease when the pore volume is less than the above range is avoided, and the problem that may occur when the pore volume is greater than the above range is avoided: that is, although a larger discharge capacity and high-load characteristics can be expected, the porous carbon structure may have a lower strength. The lower limit of the pore volume is preferably 4.0 cm 3 / g or more and more preferably 4.1cm 3 / g or more, and the upper limit of the pore volume is preferably 10.0 cm 3 / g or less and more preferably 9.0 cm 3 / g or less. Such a value can enable a larger discharge capacity and high load characteristics. Therefore, even larger discharge capacity and high load characteristics can be achieved, and the porous carbon structure is easily self-supporting.

[0117] The "porosity" in the above condition (d) is determined from the apparent density and true density of the porous carbon structure according to the following calculation formula: (1-apparent density of porous carbon structure / true density of constituent material of porous carbon structure)×100.

[0118] The "porosity" of the porous carbon structure of the present invention is within the range of the above condition (d) (i.e., the total porosity is within the range of 80% to 99%), which means that the porous carbon structure has a sufficiently high porosity. When such a porous carbon structure is used in the positive electrode of an air battery, a large amount of lithium peroxide generated by discharge can be stored, and air or oxygen enters the positive electrode from the outside of the battery smoothly with less resistance, so that a battery having a high discharge capacity and capable of high-speed discharge can be provided.

[0119] Because the total porosity of the porous carbon structure of the present invention is above 80%, the problem that the porous carbon structure has lower air permeability and ion transmission efficiency and the reaction field becomes narrower when used as a positive electrode structure of a battery is avoided, which may occur when the total porosity is less than the above value.

[0120] In addition, because the total porosity of the porous carbon structure is 99% or less, problems that may occur when the total porosity is greater than the above value, such as the rigidity of the porous carbon structure is reduced, the porous carbon structure becomes brittle, and the porous carbon structure may have almost no self-supporting ability, are avoided.

[0121] When the lower limit of the total porosity is 90% or more, it is easier to avoid the problem that the generation field of lithium peroxide is reduced and the entry of air or oxygen is delayed, so that the discharge capacity and high load characteristics may be reduced. Therefore, the lower limit of the total porosity is preferably 90% or more. The lower limit of the porosity is more preferably 91% or more, and even more preferably 92% or more.

[0122] The upper limit of the porosity is not particularly limited, but is preferably 99% or less, and more preferably 98% or less.

[0123] There are no particular restrictions on other requirements of the porous carbon structure of the present invention as long as the porous carbon structure satisfies all of the above conditions (a) to (d).

[0124] The porous carbon structure of the present invention may contain carbon fibers 13. In one example, the carbon fibers 13 may have a fiber diameter of 0.1 μm to 20 μm and a length of 1 mm to 20 mm. This may improve the strength of the porous carbon structure.

[0125] The porous carbon structure of the present invention preferably satisfies the above condition (e) "the pore volume of pores with a diameter of 200 nm or more and 10,000 nm or less is within 2.3 cm 3 / g or more and 8.0cm 3 / g or less".

[0126] The above condition (e) "the pore volume of pores with a diameter of 200 nm or more and 10,000 nm or less is within 2.3 cm 3 / g or more and 8.0cm 3 / g range" corresponds to the pore image Figure 2 and Figure 8 The pore volume of pores having a diameter of 200 nm or more and 10,000 nm or less was determined using a value obtained by mercury intrusion porosimetry.

[0127] The pores within this range are mainly used to enable oxygen outside the battery to enter the interior of the porous carbon structure as the positive electrode. Because the pore volume within this range is large enough, a sufficient amount of oxygen can enter at a high speed in the process in which lithium reacts with oxygen to produce lithium peroxide. Therefore, using the porous carbon structure of the present invention in the positive electrode can provide a battery with a large discharge capacity at a high current density, that is, a battery with excellent high-load characteristics. In addition, during charging, lithium peroxide transfers electrons to the electrode and decomposes into Li ions and oxygen. Because the pore volume of pores with a diameter of 200nm or more and 10,000nm or less is within the above range, the generated oxygen is more likely to leave the porous carbon structure, and high-speed charging becomes possible.

[0128] Since the pore volume of pores with a diameter of 200 nm or more and 10,000 nm or less is within the range of the above condition (e) (at 2.3 cm 3 / g or more and 8.0cm 3 / g or less), so that the problem that the oxygen inlet rate is reduced and the high load characteristics may be reduced, which may occur when the pore volume is smaller than the above range, is avoided, and the problem that the porous carbon structure may have lower strength, which may occur when the pore volume is larger than the above range, is avoided. The lower limit of the pore volume is preferably 2.5 cm 3 / g or more and more preferably 2.6cm 3 / g or more, and the upper limit of the pore volume is preferably 7.0 cm 3 / g or less and more preferably 6.5cm 3 / g or less. Such a value can enable the battery to have high load characteristics. Such a value can enable the battery to have high load characteristics while maintaining the strength of the porous carbon structure.

[0129] The pore volume of pores having a diameter of 1 nm or more and 200 nm or less in the above condition (b) and the pore volume of pores having a diameter of 200 nm or more and 10,000 nm or less in the above condition (e) are not particularly limited as long as the pore volumes are respectively within the above ranges. However, it is more preferred that the pore volume of pores having a diameter of 200 nm or more and 10,000 nm or less in the above condition (e) is substantially the same as the pore volume of pores having a diameter of 1 nm or more and 200 nm or less in the above condition (b), and it is still more preferred that the pore volume of pores having a diameter of 200 nm or more and 10,000 nm or less in the above condition (e) is greater than the pore volume of pores having a diameter of 1 nm or more and 200 nm or less in the above condition (b). The pores with a diameter of 200 nm or more and 10,000 nm or less in the above condition (e) are mainly used to allow oxygen outside the battery to enter the interior of the porous carbon structure as the positive electrode during the discharge process, and to allow oxygen generated during the charging process to leave the porous carbon structure, and to store lithium peroxide generated during the discharge process. Therefore, when the pore volume of the pores with a diameter of 200 nm or more and 10,000 nm or less in the above condition (e) is equal to or greater than the pore volume of the pores with a diameter of 1 nm or more and 200 nm or less in the above condition (b), a battery having both high-speed charge-discharge characteristics and high-capacity characteristics can be obtained.

[0130] The apparent density of the porous carbon structure of the present invention is preferably 0.05 g / cm 3 Above and 0.20g / cm 3 When the apparent density of the porous carbon structure is within the above range, the porous carbon structure has sufficient pores for the permeation and diffusion of oxygen and has sufficient strength. As described above, because the porous carbon structure of the present invention has a self-supporting ability, the porous carbon structure can be used as a positive electrode of an air battery without using a metal mesh or the like. This makes it possible to reduce the weight and size of the battery, improve productivity, and reduce costs.

[0131] Specifically, since the apparent density is within the above range (0.05 g / cm 3 Above and 0.20g / cm 3 The following range) is avoided, so that the strength of the porous carbon structure may be reduced and the porous carbon structure may need to be attached to a current collector such as a metal mesh to form a positive electrode, which may occur when the apparent density is less than the above range, and the problem that the amount of pores in the porous carbon structure may be small and the capacity and load characteristics may be reduced, which may occur when the apparent density is greater than the above range, is avoided. The lower limit of the apparent density is preferably 0.07 g / cm 3 More preferably 0.09 g / cm 3The upper limit of the apparent density is preferably 0.18 g / cm 3 Less than and more preferably 0.17 g / cm 3 As a result, the porous carbon structure can have pores and high strength. As a result, the porous carbon structure of the present invention can also have more pores and higher strength.

[0132] The skeleton mainly contains carbon. More preferably, the skeleton contains carbon in an amount of preferably 90% by weight or more and more preferably 93% by weight or more. When the amount of carbon is 90% by weight or more, it is easy to improve the ion transmission efficiency, and when used as a positive electrode structure of a battery, the reaction field is easy to widen.

[0133] In addition, the skeleton preferably contains conductive carbon, and more preferably is made of conductive carbon. Because the skeleton contains conductive carbon or is made of conductive carbon, the porous carbon structure improves conductivity, and the battery using the porous carbon structure as the positive electrode structure improves conductivity. As a result, the internal resistance of the battery is reduced, and the output of the battery is improved.

[0134] The content of fluorine (F) in the porous carbon structure of the present invention can be 0.002 mg or less per 1 g of the porous carbon structure (less than 0.0002 mass %). In the porous carbon structure of the present invention, since it is not necessary to use a fluorine-containing polymer binder as a bonding polymer material, the content of fluorine can be set to be equal to or less than the above value.

[0135] The BET specific surface area of ​​the porous carbon structure of the present invention is preferably 300 m 2 / g or more and 1,600m 2 / g or less. Because the BET specific surface area of ​​the porous carbon structure is within the above numerical range, the problem that the porous carbon structure has lower air permeability and ion transmission efficiency and the reaction field becomes narrower when used as the positive electrode structure of the battery is avoided when the BET specific surface area is less than the above numerical range, and the problem that the rigidity of the structure is reduced, the porous carbon structure becomes brittle, and the porous carbon structure has almost no self-supporting ability that may occur when the BET specific surface area is greater than the above numerical range is also avoided. When the above problem is avoided, in the case where the porous carbon structure needs to be used as the positive electrode structure, because the porous carbon structure is self-supporting, it is not necessary to make the porous carbon structure a powder and support the powder in a metal electrode container, etc. Therefore, it is possible to reduce the weight and size of the battery, improve productivity, and reduce costs.

[0136] The lower limit of the BET specific surface area is more preferably 400 m 2 / g or more, and more preferably 500 m 2 / g or more, and the upper limit of the BET specific surface area is more preferably 1,500 m 2 / g or less, and still more preferably 1,400m / g or less 2 / g or less.

[0137] In the porous carbon structure of the present invention, the SA ratio (=[t-curve external specific surface area / BET specific surface area (=t-curve external specific surface area+t-curve micropore specific surface area)]×100) is preferably 30% or more.

[0138] When the SA ratio satisfies the above value, problems that may occur when the SA ratio is less than the above value, namely, a reduction in the reaction field when the porous carbon structure is used as a positive electrode structure of a battery, and a reduction in air permeability and ion transmission efficiency are avoided.

[0139] <Second Implementation Method>

[0140] In the second embodiment, an exemplary method for producing the porous carbon structure of the present invention will be described.

[0141] The porous carbon structure of the present invention can be obtained by a manufacturing method comprising the following steps: preparing a mixture slurry containing porous carbon particles and a bonding polymer material, molding the mixture slurry, impregnating the sample obtained by the molding step in a solvent in which the bonding polymer material has low solubility, drying the sample obtained by the impregnation step, and carbonizing the sample obtained by the drying step. In the carbonization step during the manufacturing process, for example, the carbonization is performed in an atmosphere of an oxidizing gas or an inert gas.

[0142] Figure 4 is a flow chart showing a method for making the porous carbon structure of the present invention.

[0143] First, a mixture slurry is prepared (step S1).

[0144] The mixture preferably contains 50 wt % or more and 85 wt % or less of porous carbon particles, 1 wt % or more and 15 wt % or less of carbon fibers, 5 wt % or more and 49 wt % or less of a binding polymer material, and a solvent for uniformly dispersing these materials.

[0145] Carbon fibers are not necessarily required, but are more preferably contained because the carbon fibers exhibit an effect of reinforcing the porous carbon structure.

[0146] As the porous carbon particles, carbon black including Ketjen Black (registered trademark) can be used, and in addition, carbon particles formed by a template method and the like can be used.

[0147] The porous carbon particles preferably meet the following conditions: the BET specific surface area is 1,000 m 2 / g or more and 1,500m 2 / g or less, and the pore volume of pores with a diameter of 1 nm or more and 1,000 nm or less is within 3.0 cm 3 / g or more and 4.0cm 3 / g or less, the pore volume of pores with a diameter of 1 nm or more and 200 nm or less is within 2.0 cm 3 / g or more and 3.0cm 3 Use of such porous carbon particles as a raw material makes it easier to obtain a porous carbon structure that satisfies the above conditions (a) to (d).

[0148] As the carbon fiber, carbon fibers having a fiber diameter of 0.1 μm or more and 20 μm or less and a length of 1 mm or more and 20 mm or less can be used.

[0149] As the bonding polymer material, a polymer material such as polyacrylonitrile (PAN), polysulfone, or solvent-soluble polyimide can be used. In view of environmental issues, etc., it is preferable to use a polymer material that does not contain fluorine (F) element.

[0150] Examples of the solvent include dimethyl sulfoxide (DMSO), N-methylpyrrolidone (NMP), dimethylformamide (DMF), and dimethylacetamide (DMA).

[0151] Next, a forming (molding) step (step S2) is performed.

[0152] The molding method of the mixture slurry is not particularly limited, and examples thereof include a wet film-forming method using a well-known doctor blade and the like.

[0153] Examples of the molding method also include a roll coating method, a die coating method, a spin coating method, and a spray coating method.

[0154] The shape after molding can have various shapes according to the purpose. For example, the mixture slurry is formed into a sheet shape with uniform thickness.

[0155] Thereafter, a solvent immersion step is performed (step S3).

[0156] In the solvent immersion step, the sample, which means the molded body obtained in step S2, is immersed in a solvent in which the binding polymer material has low solubility by a non-solvent-induced phase separation method. Through this step, a porous membrane is formed.

[0157] Examples of the solvent include water, alcohols such as ethanol, methanol and isopropanol, and mixed solvents thereof.

[0158] Among them, water is preferred from the viewpoint of excellent operability, and alcohol is preferred from the viewpoint that a battery prepared using the finally produced porous carbon structure has a characteristic of high discharge capacity.

[0159] Next, a drying step is performed (step S4).

[0160] In this step, the solvent is volatilized from the molded body (porous membrane) obtained in step S3. Examples of drying methods include a method of placing the molded body in a dry air environment, a reduced pressure drying method, and a vacuum drying method. In this drying step, in order to increase the drying speed, heating can be performed at a temperature exceeding the boiling point of the solvent.

[0161] Next, an infusibility treatment step is performed (step S5).

[0162] This treatment is carried out to prevent the bonding polymer material from melting and separating in the subsequent carbonization treatment step and deforming the shape of the molded body. Specifically, the infusible treatment can be achieved by oxidative crosslinking the bonding polymer material to solidify the bonding polymer material. The infusible treatment is carried out by heating with a furnace, infrared radiation, etc. under air flow. The temperature is preferably above 250°C and below 350°C. When the temperature is set to above 250°C, the problem that the oxidative crosslinking of the bonding polymer material may be insufficient and the bonding polymer material may melt in the subsequent carbonization step is avoided. When the temperature is set to below 350°C, the problem of possible decomposition of the bonding polymer material is avoided. Depending on the type of bonding polymer material used or the type of oxidizing gas in the subsequent carbonization treatment step, this step can be omitted.

[0163] Next, a carbonization treatment step is performed (step S6).

[0164] Through this treatment, the binding polymer is polycondensed to become carbon, and this carbon strongly binds the porous carbon particles to each other. Through the carbonization treatment, a porous carbon structure having a self-supporting ability is produced.

[0165] The carbonization treatment is not particularly limited as long as the above-mentioned purpose can be achieved, but for example, the carbonization treatment can be carried out in an atmosphere of an oxidizing gas or an inert gas. In this case, the carbonization treatment is preferably carried out in an oxidizing gas atmosphere. More preferably, the carbonization treatment is carried out in an oxidizing gas atmosphere and then another carbonization treatment is carried out in an inert gas atmosphere. The carbonization treatment carried out in an oxidizing gas atmosphere burns and removes a portion of the bonding polymer material, and further burns and removes a portion of the porous carbon particles as a raw material, and the bonding polymer retained between the porous carbon particles is carbonized to firmly bind the porous carbon particles to each other.

[0166] First, a case where the carbonization treatment step (carbonization treatment step) is performed in an oxidizing gas atmosphere will be described.

[0167] When the carbonization treatment step (carbonization treatment step) is performed in an oxidizing gas atmosphere, for example, the product obtained in step S4 or step S5 is preferably heat-treated in an oxidizing gas having an oxygen concentration in the range of more than 0.03% and less than 5%. In the present application, from such a point of view, the carbonization treatment in an oxidizing gas atmosphere may be simply referred to as oxidation treatment.

[0168] The oxidizing gas atmosphere may preferably be a gas containing oxygen, air, water or carbon dioxide (CO2). These gases can burn and remove most of the binding polymer material, and further burn and remove a portion of the porous carbon particles. The oxidizing gas atmosphere more preferably also contains an inert gas, such as argon (Ar), nitrogen (N2) or helium (He).

[0169] When the carbonization treatment step (carbonization treatment step) is performed in an oxidizing gas atmosphere, the oxygen concentration is preferably set in the range of greater than 0.03% and less than 5% as described above. From the viewpoint of achieving the above-mentioned purpose of the carbonization treatment, an oxygen concentration in the range of greater than 0.03% and less than 5% is preferred. This is because the problem that the oxidation treatment tends not to proceed, which may occur when the oxygen concentration is less than the above range, is avoided, and the problem that the porous carbon structure may be excessively burned and split by the oxidizing gas or may have insufficient strength, which may occur when the oxygen concentration is greater than the above range, is avoided. The oxygen concentration is more preferably in the range of more than 0.04% and less than 4%. At an oxygen concentration within the above range, the oxidation treatment is more efficiently performed. The oxygen concentration is still more preferably in the range of more than 0.05% and less than 4%. At an oxygen concentration within the above range, the oxidation treatment is even more efficiently performed, and the porous carbon structure of the present invention can be obtained with high efficiency. The oxygen concentration is still more preferably in the range of more than 0.2% and less than 2%. At an oxygen concentration within the above range, oxidation treatment proceeds even more efficiently, and the porous carbon structure of the present invention can be obtained with higher efficiency and high yield.

[0170] When water is used as the oxidizing gas atmosphere, the oxygen concentration is a concentration based on the amount of oxygen calculated from oxygen atoms contained in water.

[0171] The carbonization treatment can be performed in a state where the oxidizing gas is sealed in the furnace, or can be performed while the oxidizing gas is made to flow in the furnace. When the oxidizing gas is made to flow, the flow rate is not particularly limited, but is preferably 0.1 mL / min or more and 100 3 When the flow rate is less than the above range, oxidation may be difficult to carry out, and when the flow rate is greater than the above range, it may be disadvantageous in terms of cost. The flow rate is more preferably above 1 mL / min and 100 3 The range of 10 mL / min or less is still more preferably 10 mL / min or more and 103 Within the range below L / min.

[0172] The furnace used in the carbonization treatment is not particularly limited as long as the oxidizing gas can be sealed or flowed in the furnace, but a baking furnace, a tube furnace, a box furnace, an infrared radiation furnace, a graphite heating furnace, an induction heating furnace, a plumb furnace, an Atchison furnace, etc. can be used.

[0173] The temperature of the carbonization treatment is preferably in the temperature range of 350°C to 3,000°C. When the temperature of the carbonization treatment is in the temperature range of 350°C to 3,000°C, the problem that a sufficient oxidation effect may not be obtained, which may occur when the temperature is lower than the above temperature range, and the problem that the porous carbon structure may burn and burn out, which may occur when the temperature is higher than the above temperature range, are avoided. The temperature of the carbonization treatment is more preferably in the range of 400°C to 2000°C and even more preferably in the range of 420°C to 1500°C.

[0174] The upper limit of the heating rate in the carbonization treatment is preferably 100°C / min or less, more preferably 50°C / min or less, and even more preferably 30°C / min or less. When the heating rate in the carbonization treatment is set as described above, the problem that the porous carbon structure tends to be insufficiently oxidized, which may occur when the heating rate is greater than the above value, is avoided. The lower limit of the heating rate is not particularly limited, but is preferably 0.01°C / min or more from a cost perspective.

[0175] Preferably, the carbonization treatment step is carried out until the pore volume of pores with a diameter of 1 nm or more and 1,000 nm or less in the product obtained by the carbonization treatment (i.e., the porous carbon structure of the present invention) increases to a level greater than the pore volume of pores with a diameter of 1 nm or more and 1,000 nm or less in the porous carbon used as the raw material.

[0176] Specifically, it is preferred to perform the carbonization treatment step until the increase factor of the pore volume is in the range of 1.02 times or more and 10.0 times or less. When the increase factor of the pore volume is less than the above range, a sufficient oxidation effect may not be obtained, and when the increase factor of the pore volume is greater than the above range, a porous carbon structure having sufficient strength may not be obtained. The increase factor of the pore volume is more preferably in the range of 1.04 times or more and 8.0 times or less, and is still more preferably in the range of 1.05 times or more and 5.0 times or less.

[0177] The porous carbon structure of the present invention is obtained by the step of performing the carbonization treatment in the oxidizing gas atmosphere (step S6) as described above (step S7), and the carbonization treatment step may also be performed in an inert gas atmosphere instead of the oxidizing gas atmosphere.

[0178] A case where the carbonization treatment step (carbonization treatment step) is performed in an inert gas atmosphere instead of an oxidizing gas atmosphere will be described.

[0179] In this case, similar to the case of carrying out the carbonization treatment step in an oxidizing gas atmosphere, the furnace used in the carbonization treatment is not particularly limited as long as the inert gas can be sealed or flowed in the furnace, but a baking furnace, a tubular furnace, a box furnace, an infrared radiation furnace, a graphite heating furnace, an induction heating furnace, a plumb furnace, an Atchison furnace, etc. can be used.

[0180] The temperature of the carbonization treatment is preferably in the range of 800° C. to 3000° C. In this temperature range, the problem of not being able to obtain a sufficient carbonization effect is avoided. The temperature of the carbonization treatment is more preferably in the range of 900° C. to 2500° C.

[0181] Similar to the case where the carbonization treatment step is performed in an oxidizing gas atmosphere, the upper limit of the heating rate in the carbonization treatment is preferably 100°C / min or less, more preferably 50°C / min or less, and even more preferably 30°C / min or less. When the heating rate is set as described above, the problem that the porous carbon structure tends to be insufficiently carbonized, which may occur when the heating rate is greater than the above value, is avoided. The lower limit of the heating rate is not particularly limited, but is ideally 0.01°C / min or more from a cost perspective.

[0182] The inert gas atmosphere is specifically a rare gas such as argon (Ar), nitrogen (N2) and the like.

[0183] The porous carbon structure of the present invention (step S7) is obtained by the step of carbonizing in an oxidizing gas atmosphere as described above (step S6), and after the carbonizing step (step S6) and before the step of obtaining the porous carbon structure of the present invention (step S7), the porous carbon structure may be subjected to additional carbonization treatment under an inert gas atmosphere. As a result, the bonding polymer material remaining in the contact portion between the porous carbon particles and involved in the bonding between the porous carbon particles is carbonized, thereby making it possible to further improve the strength of the porous carbon structure, and to improve the electronic conductivity of the porous carbon structure.

[0184] The inert gas atmosphere is a rare gas such as argon (Ar), nitrogen (N2), etc. In particular, when the carbonization treatment in the oxidizing gas atmosphere is performed at a temperature below 800°C, it is preferred to subsequently perform the carbonization treatment step in the inert gas atmosphere. As a result, the bonding polymer material remaining in the contact portion between the porous carbon particles and involved in the bonding between the porous carbon particles is carbonized, thereby making it possible to further improve the strength of the porous carbon structure, and improve the electronic conductivity of the porous carbon structure.

[0185] Regarding the carbonization treatment step in an inert gas atmosphere, the atmosphere may be switched to an inert gas directly after the carbonization treatment in an oxidizing gas atmosphere (step S6), and the temperature may be raised to a predetermined carbonization temperature. In addition, the porous carbon structure may be taken out after the carbonization treatment in an oxidizing gas atmosphere (step S6), and then the porous carbon structure may be subjected to another carbonization treatment in an inert gas atmosphere.

[0186] The temperature of the carbonization treatment in the inert gas atmosphere is preferably 800° C. or higher, and more preferably 900° C. or higher. The upper limit of the temperature is not particularly limited, but is preferably 3,000° C. or lower in view of cost.

[0187] Through the above steps, a porous carbon structure having sufficient and practical mechanical strength due to its self-supporting ability is manufactured. The molded body is completely carbonized by the above heat treatment, and a porous carbon structure having self-supporting ability and electronic conductivity required for the electrode and excellent oxidation resistance can be provided without using a resin binder or a current collector mesh that is not directly involved in the secondary battery reaction. The porous carbon structure has self-supporting ability and has high air or oxygen permeability, high ion transmission efficiency and a wide reaction field.

[0188] In particular, the carbonization treatment in the oxidizing gas atmosphere in step S6 burns and removes the bonding polymer material covering the surface of the porous carbon particles as the raw material constituting the porous carbon structure, so that the pore volume and specific surface area of ​​the pores originally possessed by the porous carbon particles become apparent. In addition, a portion of the porous carbon particles themselves are also oxidized, so that the pore volume and specific surface area of ​​the pores of the obtained porous carbon structure are increased to a pore volume and specific surface area greater than the pore volume and specific surface area of ​​the pores originally possessed by the porous carbon particles as the raw material. Because a portion of the bonding polymer material and the porous carbon particles are burned, the space between the particles increases accordingly. In addition, the manufactured porous carbon structure has sufficient and practical mechanical strength due to its self-supporting ability. This shows that the bonding polymer between the porous carbon particles involved in the bonding between the porous carbon particles is carbonized by the carbonization treatment, while still involving the bonding between the porous carbon particles. That is to say, it can be understood that the bonding polymer involved in the bonding between the porous carbon particles exists between the tightly bound particles in a state of being carbonized by the carbonization treatment, so oxygen cannot enter. On the other hand, it is understood that oxygen reaches the polymer on the surface of the porous carbon particles without involving bonding with other particles through the mesopores and macropores formed in the porous carbon structure, and the polymer is oxidized and burned.

[0189] The porous carbon structure of the present invention has a reduced H / C ratio because hydrogen (H) is desorbed and cyclized through the carbonization step. In addition, through carbonization, the porous carbon particles used as a raw material also have a reduced amount of H due to the formation of a covalent carbon network surface. The carbonization step of the present invention can provide a porous carbon structure with excellent oxidation resistance.

[0190] As described above, the amount of fluorine (F) contained in the porous carbon structure of the present invention can be 0.002 mg or less per 1 g of the porous carbon structure (0.0002 mass % or less). In the porous carbon structure of the present invention, since it is not necessary to use a fluorine-containing polymer binder as a bonding polymer material, the amount of fluorine can be set to be equal to or less than the above value.

[0191] On the other hand, in the generally introduced lithium ion battery and lithium-air battery, generally, a fluorine-based polymer material having excellent oxidation resistance is used as a binder used in the material of the positive electrode.

[0192] However, since the porous carbon structure of the present invention is obtained through the carbonization step even when a non-fluorine-based binder is used as the binding polymer material, the binder component is carbonized, so that a structure having excellent oxidation resistance is formed.

[0193] <Third Implementation Method>

[0194] In a third embodiment, reference is made to Figure 5 and 6 A coin cell using the porous carbon structure described in the first embodiment as a positive electrode structure is described.

[0195] Figure 5 is a schematic diagram showing a button battery.

[0196] Figure 6 is a schematic diagram showing another type of button battery.

[0197] The button cell 600 in the third embodiment includes a laminated structure in which a negative electrode structure 610 and a positive electrode structure 620 are laminated with a separator 660 interposed therebetween. The laminated structure is restrained by a button cell type restraining tool 630. An insulating O-ring (not shown) is arranged between the button cell type restraining tool 630 and the metal mesh 680, and ensures insulation between the restraining tool 630 and the positive electrode structure 620.

[0198] As can be understood from the fact that the air battery is named in the sense that oxygen in the air is used as the positive electrode active material of the battery, it is necessary to supply at least 21% of oxygen (which is the oxygen concentration in the air). However, in order to reduce the influence of diffusion control, a higher concentration of oxygen is preferred, and the air battery can exhibit the highest characteristics by supplying pure oxygen.

[0199] The negative electrode structure 610 may be a commonly used negative electrode structure. Examples of the negative electrode structure include a structure having a current collector 635 and a metal layer 640 containing an alkali metal and / or an alkaline earth metal, wherein the metal layer 640 is disposed on the current collector 635. Here, the metal layer 640 may generally be a layer made of lithium metal.

[0200] The positive electrode structure 620 includes the porous carbon structure 690 described in the first embodiment, wherein the porous carbon structure 690 is in mechanical and electrical contact with a metal-containing mesh (metal mesh) 680 serving as both a flow path for air or oxygen to pass through and a current collector.

[0201] Alternatively, Figure 6 As shown in the button cell 601 in FIG. 6 , the positive electrode structure 621 includes only the porous carbon structure 690 described in the first embodiment. Here, the difference between the button cell 600 and the button cell 601 is only the presence or absence of the metal mesh 680. An insulating O-ring (not shown) is arranged between the button cell type confinement tool 630 and the porous carbon structure 690, and ensures insulation between the confinement tool 630 and the positive electrode structure 621.

[0202] Here, since the positive electrode structure 620 including the metal mesh 680 improves conductivity and sufficiently ensures a flow path for air or oxygen, it is a structure suitable for high output.

[0203] In contrast, since the positive electrode structure 621 composed only of the porous carbon structure 690 does not include a metal mesh as a current collector, it is a structure that provides a high weight energy density of the battery, has a simple structure, is manufactured with a reduced number of steps, and can be efficiently manufactured. As described above, since the porous carbon structure 690 is a self-supporting body with sufficient rigidity, the porous carbon structure 690 can even be used alone as the positive electrode structure 621.

[0204] Preferably, a groove (not shown) is formed in the porous carbon structure 690 to ensure an additional flow path for air or oxygen to pass through. Because the porous carbon structure 690 of the present invention has sufficient strength, a groove for the flow of air or oxygen can be provided. The width of the groove can be, for example, more than 0.1 mm and less than 3 mm. When the width of the groove is less than 0.1 mm, the flow of air or oxygen is reduced. Even when the width of the groove is greater than 3 mm, there is no big difference in the flow of air or oxygen, but the strength of the porous carbon structure 690 becomes lower, and the porous carbon structure 690 is easily damaged. Preferably, a plurality of grooves are formed, and it is also necessary to form the grooves in a grid pattern.

[0205] The separator 660 is disposed between the negative electrode structure 610 and the positive electrode structure 620. A spacer 650 is formed between the separators 660 covering the metal layer 640. In addition, a space 670 is formed between the metal layer 640, the spacer 650, and the separator 660, and the space 670 is filled with an electrolyte solution.

[0206] Next, a method for manufacturing the button cell 600 will be described.

[0207] First, the negative electrode structure 610 is prepared. For example, the negative electrode structure 610 is manufactured and prepared as follows.

[0208] On the disk-shaped current collector 635, a disk-shaped metal layer 640 made of lithium or the like is laminated, wherein the disk-shaped metal layer 640 is concentric with the current collector 635 and has a diameter smaller than that of the current collector 635, and then the columnar spacer 650 is pressed onto the current collector 635 to obtain the negative electrode structure 610.

[0209] Here, examples of the material of the spacer 650 include metal oxides, metal nitrides, and metal oxynitrides having insulating properties. Examples thereof include inorganic materials selected from the group consisting of: Al2O3, Ta2O5, TiO2, ZnO, ZrO, SiO2, B2O3, P2O5, GeO2, Li2O, Na2O, K2O, MgO, CaO, SrO, BaO, Si3N4, AlN, and AlO x N 1-x (0 < x < 1). Among them, in particular, Al2O3 and SiO2 are easily obtained and have excellent processability characteristics.

[0210] In one example, the spacer 650 can be made of an organic material selected from the group consisting of: polyolefin resins, polyester resins, polyimide resins, and polyether ether ketone (PEEK) resins. The polyolefin resin is preferably polyethylene and / or polypropylene. The polyester resin is preferably selected from the group consisting of: polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polyethylene naphthalate (PEN), and polytrimethylene terephthalate (PTT). These resins are easily obtained and have excellent processability.

[0211] Next, the separator 660 is prepared and pressed onto the spacer 650.

[0212] The material applied to the separator 660 is any inorganic material, organic material, or metal material that can pass alkali metal ions and / or alkaline earth metal ions, is an insulating material having a porous structure, and does not react with the metal layer 640 and the electrolyte solution.

[0213] There is no particular limitation as long as these conditions are satisfied, and a separator used in an existing metal battery may be used. For example, the separator 660 is selected from the group consisting of: a porous film made of a synthetic resin such as polyethylene, polypropylene, or polyolefin; glass fiber; and nonwoven fabric.

[0214] It is preferable to provide a space 670 between the lithium metal 640 , the spacer 650 , and the separator 660 .

[0215] Thereafter, the separator 660 is filled with the electrolyte. In this case, the space 670 is also preferably filled with the electrolyte.

[0216] When a lithium salt is used as an alkali metal salt and / or an alkaline earth metal salt in a non-aqueous electrolyte, examples of the lithium salt include LiPF6, LiBF4, LiSbF6, LiSiF6, LiAsF6, LiN(SO2C2F5)2, Li(FSO2)2N, LiCF3SO3(LiTfO), Li(CF3SO2)2N(LiTFSI), LiC4F9SO3, LiClO4, LiAlO2, LiAlCl4 and LiB(C2O4)2.

[0217] In the non-aqueous electrolyte, the non-aqueous solvent is selected from the group consisting of glycol dimethyl ethers (monoglycol dimethyl ether, diglycol dimethyl ether, triglycol dimethyl ether and tetraglycol dimethyl ether), methyl butyl ether, diethyl ether, ethyl butyl ether, dibutyl ether, polyethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, cyclohexanone, di alkane, dimethoxyethane, 2-methyltetrahydrofuran, 2,2-dimethyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, tetrahydrofuran, methyl acetate, ethyl acetate, n-propyl acetate, dimethyl acetate, methyl propionate, ethyl propionate, methyl formate, ethyl formate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, dipropyl carbonate, methylpropyl carbonate, ethylpropyl carbonate, ethylene carbonate, propylene carbonate, butylene carbonate, polyethylene carbonate, gamma-butyrolactone, decanoic acid, valerolactone, mevalerolactone, caprolactone, acetonitrile, benzonitrile, nitromethane, nitrobenzene, triethylamine, triphenylamine, tetraethylene glycol diamine, dimethylformamide, diethylformamide, N-methylpyrrolidone, dimethyl sulfone, tetramethylene sulfone, triethylphosphine oxide, 1,3-dioxolane and sulfolane.

[0218] Thereafter, a positive electrode structure 620 in which a metal mesh is arranged on the porous carbon structure 690 prepared by the manufacturing method described in the first embodiment is prepared.

[0219] Examples of the metal mesh 680 include a mesh containing a metal selected from the group consisting of copper (Cu), tungsten (W), aluminum (Al), nickel (Ni), titanium (Ti), gold (Au), silver (Ag), platinum (Pt), and palladium (Pd). That is, examples of the metal mesh 680 include a mesh containing a single metal selected from the above group, an alloy containing a metal selected from the above group, or a compound of a metal selected from the above group and carbon (C), nitrogen (N), etc. For example, the mesh may have a thickness of 0.2 mm and a pore size of 1 mm.

[0220] Thereafter, the positive electrode structure 620 is adhered to the negative electrode structure 610 filled with the electrolyte via the separator 660 interposed therebetween, and the resultant is restrained with a button cell type restraining tool 630 to obtain a button cell 600. Here, the mounting is preferably performed under dry air, for example, under dry air with a dew point temperature of -50°C or less.

[0221] Through the above steps, the button battery 600 operating as an air battery is manufactured.

[0222] In the case of manufacturing the button cell 601 , in the above steps, it is only necessary to replace the positive electrode structure 620 to be prepared with the porous carbon structure 690 .

[0223] The button cells 600 and 601 become air batteries that can be reduced in size and weight and are suitable for increasing capacity. This is because in addition to the positive electrode structure 690 using the porous carbon structure described in the first embodiment having high air or oxygen permeability, being able to absorb a large amount of oxygen, and also having high ion transmission efficiency and a wide reaction field at the same time, its structure is a simple structure that can be reduced in size, which is a porous carbon structure alone or a porous carbon structure on which a metal mesh is arranged.

[0224] <Fourth Implementation Plan>

[0225] In a fourth embodiment, reference will be made to Figure 7 Describes a laminated metal battery (air battery) using the porous carbon structure described in the first embodiment as a positive electrode structure, Figure 7 is a schematic diagram showing a cross section of the air battery.

[0226] Figure 7 is a schematic diagram showing a laminated metal battery (air battery).

[0227] The air battery 500 in the fourth embodiment has a laminated structure in which a positive electrode structure 510 and a negative electrode structure 100 are laminated via a separator 540 interposed therebetween. The number of laminated layers may be one or more pairs, and there is no particular upper limit to the number of pairs. Here, a pair is formed by one positive electrode structure 510 and one negative electrode structure 100, and this is defined as one unit.

[0228] Here, the negative electrode structure 100 has a configuration in which the negative electrode structure 610 described in the third embodiment is arranged above and below the negative electrode collector electrode 520 interposed therebetween, and the positive electrode structure 510 also has a configuration in which the porous carbon structure 690 described in the first embodiment is arranged above and below the positive electrode collector electrode 525 interposed therebetween, wherein the positive electrode collector electrode 525 also serves as a flow path for air or oxygen. Forming a battery capable of providing a larger capacity by such a simple laminated structure is also a characteristic unique to the porous carbon structure positive electrode having a self-supporting ability.

[0229] Examples of negative current collector electrodes 520 include electrodes containing metals selected from the group consisting of copper (Cu), tungsten (W), nickel (Ni), titanium (Ti), gold (Au), silver (Ag), platinum (Pt) and palladium (Pd). Examples of positive current collector electrodes 525 include electrodes containing metals selected from the group consisting of stainless steel (SUS), tungsten (W), aluminum (Al), nickel (Ni), titanium (Ti), gold (Au), silver (Ag), platinum (Pt) and palladium (Pd). That is, examples of current collector electrodes 520 and 525 include electrodes containing the following: simple metals selected from this group, alloys containing metals selected from this group, or compounds of metals selected from this group with carbon (C), nitrogen (N), etc. Because the positive current collector electrode 525 is also used as an oxygen flow path, porous metals such as nets, grids or sponges must be used. The laminated structure is contained in a container (not shown).

[0230] The air battery 500 is an air battery capable of being reduced in size and weight and suitable for increasing capacity. This is because, in addition to the positive electrode structure 510 using the porous carbon structure described in the first embodiment having high air or oxygen permeability, capable of absorbing a large amount of oxygen, and also having high ion transmission efficiency and a wide reaction field at the same time, its structure is a simple structure capable of being reduced in size, which is a porous carbon structure alone or a porous carbon structure on which a metal mesh is arranged.

[0231] In the fourth embodiment, although reference has been made to Figure 7 An air battery using the positive electrode structure 510 of the present invention is described, but the positive electrode structure 510 of the present invention may be applied to any metal battery without being limited to the air battery.

[0232] Next, the present invention will be described with reference to specific embodiments, but it should be noted that the present invention is not limited to these embodiments. Example

[0233] The preparation of samples of the porous carbon structure of the present invention and the properties of the prepared porous carbon structure samples will be described in comparison with Comparative Examples.

[0234] Hereinafter, samples referred to as porous carbon structure Nos. 1 to 8 and 10 to 16 are porous carbon structure samples of the present invention prepared in the examples, and samples referred to as porous carbon structure Nos. 9 and 17 to 25 are comparative samples (Comparative Examples).

[0235] [Example 1A: Porous carbon structure]

[0236] In Example 1A, the preparation of the porous carbon structure samples of the present invention (porous carbon structures No. 1 to 8 and 10) and the comparative sample (porous carbon structure No. 9), and the properties of the prepared porous carbon structure samples and comparative sample are described.

[0237] (Preparation of porous carbon structure)

[0238] First, a mixture slurry was prepared using the following: 65 wt% of porous carbon particles; 12 wt% of carbon fibers; 23 wt% of a bonding polymer material; and a solvent containing N-methylpyrrolidone for uniformly dispersing the above components ( Figure 4 Step S1 in ).

[0239] Here, as the porous carbon particles, Ketjen Black (registered trademark) (EC600J, manufactured by LION SPECIALTY CHEMICALS CO., LTD.) was used. The properties of Ketjen Black EC600J are shown in Table 1.

[0240] As the carbon fibers, carbon fibers having an average fiber diameter of 6 μm and an average length of 3 mm were used.

[0241] As the adhesive polymer material, polyacrylonitrile (PAN) was used.

[0242] [Table 1]

[0243] Table 1. Properties of porous carbon particles used in this paper

[0244]

[0245] The mixture slurry was formed into a sheet with uniform thickness by a wet film forming method using a doctor blade ( Figure 4 In this case, three types of molded sheets having a thickness of 300 μm, 500 μm or 600 μm were prepared.

[0246] After the mixture slurry was molded, the molded sample was immersed in methanol (a poor solvent) by a non-solvent-induced phase separation method to form a porous membrane ( Figure 4Step S3 in the step). The non-solvent-induced phase separation method is a method in which a polymer solution is immersed in a non-solvent to phase separate and precipitate the polymer. In Example 1A, a molded sheet in a state in which the above-mentioned Ketjen Black (registered trademark) as a porous carbon particle and the above-mentioned carbon fiber are dispersed in an N-methylpyrrolidone solution of polyacrylonitrile (PAN) as a bonding polymer material is immersed in methanol as a non-solvent (poor solvent) to phase separate and precipitate polyacrylonitrile (PAN) in a state in which the above-mentioned Ketjen Black (registered trademark) is combined with the above-mentioned carbon fiber, thereby preparing a porous film containing the above-mentioned Ketjen Black (registered trademark) as a skeleton and also containing the above-mentioned carbon fiber. In this case, most of the N-methylpyrrolidone is dissolved in methanol.

[0247] Next, a drying step is performed at 50 to 80° C. for more than 10 hours ( Figure 4 The sample was subjected to step S4 in the above method to remove the volatile solvent from the sample, followed by a heat treatment at 320° C. for 3 hours in air to prevent melting ( Figure 4 Step S5 in the process).

[0248] Then, the carbon structures having a length of 90 mm and a width of 80 mm respectively obtained by the infusible heat treatment were subjected to carbonization treatment under the ten conditions shown in the porous carbon structures No. 1 to No. 10 in Table 2 ( Figure 4 Step S6 in the above step) and further carbonization treatment, thereby obtaining ten porous carbon structures ( Figure 4 Step S7 in ).

[0249] The carbonization treatment was carried out using a box furnace manufactured by DENKEN-HIGHDENTAL Co., Ltd., and the heating rate was 10°C / min in all the following cases: the case of the carbonization treatment (oxidation treatment) in an oxidizing gas atmosphere; the case of the carbonization treatment in an inert gas atmosphere; and the case of the carbonization treatment in an oxidizing gas atmosphere and then in an inert gas atmosphere. The oxidizing gas was a mixed gas of oxygen and nitrogen. The inert gas was nitrogen.

[0250] The (fabrication) conditions for each of the samples in the preparation of porous carbon structures Nos. 1 to 10 are summarized and shown in Table 2.

[0251] [Table 2]

[0252]

[0253]

[0254]

[0255] Regarding porous carbon structures No. 1 and 4 in Table 2, carbonization was performed only while nitrogen was flowing at 800 mL / min, without oxidation treatment. Regarding porous carbon structures No. 2, 5, 6 and 8 in Table 2, carbonization was performed in the following manner: while a gas having an oxygen concentration shown in Table 2 was flowing at 800 mL / min, the temperature was raised to the oxidation temperature shown in Table 2; the gas was switched to nitrogen at this temperature, and then the temperature was raised to 1050°C in nitrogen, and the sample was kept for 3 hours; the sample was then cooled to room temperature. Regarding porous carbon structures No. 3, 7, 9 and 10 in Table 2, carbonization was performed in the following manner: while a gas having an oxygen concentration shown in Table 2 was flowing at 800 mL / min, the temperature was raised to the oxidation temperature of 1050°C shown in Table 2; the sample was kept for 2 hours, and then the gas was switched to nitrogen, and the sample was kept for 1 hour; the sample was then cooled to room temperature.

[0256] (Properties of porous carbon structures)

[0257] With respect to these samples (porous carbon structures No. 1 to 10), the yield and thickness were measured, and the self-supporting ability of the samples was observed. The results are shown together in Table 2.

[0258] In addition, the details of the sample of the porous carbon structure No. 5 were observed using a scanning electron microscope (SEM, manufactured by JEOL Ltd., JSM-7800F). The results of these observations are shown in Figure 8 and 9 Shown in.

[0259] Figure 8 is the SEM image of sample No. 5 porous carbon structure.

[0260] Fig. 9 yes Figure 8 Magnified view of the SEM image.

[0261] according to Figure 8 and 9 It has been found that the method of the present invention ( Figure 4 ) provides a porous carbon structure having a carbon-containing skeleton 10 and a large number of pores 11 and 12.

[0262] Figure 8 The pores 12 corresponding to "pores having a diameter of 200 nm or more and 10,000 nm or less" are shown, and Fig. 9 Pores 11 corresponding to “pores having a diameter of 1 nm or more and 1,000 nm or less” are shown.

[0263] The properties of each sample of the porous carbon structure Nos. 1 to 10 were examined by the following methods (1) to (10), and the results are shown in Table 3.

[0264] (1) Pore volume of pores with a diameter of 1 nm or more and 1,000 nm or less

[0265] This pore volume is determined by the BJH method from an adsorption isotherm obtained by a nitrogen adsorption method using 3Flex (manufactured by Micromeritics Instrument Corp.).

[0266] (2) Pore volume of pores with a diameter of 1 nm or more and 200 nm or less

[0267] This pore volume is determined by the BJH method from an adsorption isotherm obtained by a nitrogen adsorption method using 3Flex (manufactured by Micromeritics Instrument Corp.).

[0268] (3) Pore volume of pores with a diameter of 1 μm or more and 200 μm or less

[0269] The pore volume of pores having a diameter ranging from 10 nm to 200,000 nm (0.01 μm to 200 μm) is measured by mercury intrusion using AutoPore IV (manufactured by Micromeritics Instrument Corp.), and the value of the pore volume of pores having a pore diameter of 1 μm to 200 μm is used.

[0270] (4) BET specific surface area

[0271] The BET specific surface area was determined according to the BET method from an adsorption isotherm obtained by a nitrogen adsorption method using 3Flex (manufactured by Micromeritics Instrument Corp.).

[0272] (5) t-curve external specific surface area

[0273] The t-curve external specific surface area was determined by the t-curve method from an adsorption isotherm diagram obtained by a nitrogen adsorption method using 3Flex (manufactured by Micromeritics Instrument Corp.) and in which the layer thickness of adsorbed nitrogen was plotted on the horizontal axis and the amount of adsorbed nitrogen was plotted on the vertical axis.

[0274] (6) t-curve micropore specific surface area

[0275] The t-curve micropore specific surface area is defined as a value obtained by subtracting the t-curve external specific surface area from the specific surface area determined by the BET method.

[0276] (7) Apparent density

[0277] The apparent density is determined by dividing the weight of the porous carbon structure by the volume of the porous carbon structure.

[0278] (8) Porosity (%)

[0279] The porosity is determined by the following calculation.

[0280] (1-apparent density of porous carbon structure / real density of constituent materials of porous carbon structure)×100

[0281] (9) Pore volume of pores with a diameter of 200 nm or more and 10,000 nm or less

[0282] The pore volume of pores having a diameter ranging from 10 nm to 200,000 nm (0.01 μm to 200 μm) is measured by mercury intrusion using AutoPore IV (manufactured by Micromeritics Instrument Corp.), and the value of the pore volume of pores having a pore diameter of 200 nm to 10,000 nm is used.

[0283] (10) F content (%)

[0284] The sample was weighed and burned in an argon / oxygen mixed gas in a combustion tube of an analyzer (using AQF-2100H, GA-210 (manufactured by Mitsubishi Chemical Corporation)). The gas generated by the combustion was absorbed in an aqueous hydrogen peroxide solution, and a portion of the solution having the absorbed gas was analyzed using an ion chromatograph ICS-1600 manufactured by Dionex Corporation. The sample was weighed and measured (n=2 to 3), and the average value of the measured values ​​was determined to calculate the F content in the sample.

[0285] [Table 3]

[0286]

[0287]

[0288] As shown in Table 3, it has been found that the t-curve external specific surface area of ​​all samples of the porous carbon structures No. 1 to 8 and No. 10 is within 300 m 2 / g or more and 1,600m 2 / g or less, the pore volume of pores with a diameter of 1 nm or more and 200 nm or less is 1.2 cm 3 / g or more and 7.0cm 3 / g or less, the pore volume of pores with a diameter of 1 nm or more and 1,000 nm or less is 2.3 cm 3 / g or more and 10.0cm3 / g or less, and the total porosity is in the range of 80% or more and 99% or less, and all of the above conditions (a) to (d) are satisfied.

[0289] In contrast, it has been found that the sample of the porous carbon structure No. 9 does not satisfy all of the above conditions (a) to (d).

[0290] As shown in Table 3, it has also been confirmed that the samples of the porous carbon structures Nos. 2, 3, 5 to 8, and 10 further satisfy the requirement that the pore volume of pores having a diameter of 200 nm or more and 10,000 nm or less is 2.3 cm 3 / g or more and 8.0cm 3 / g or less, at 2.3cm 3 / g or more and 10.0cm 3 / g or less, and the pore volume of pores with a diameter of 1 nm or more and 200 nm or less is 2.2 cm 3 / g or more and 7.0cm 3 / g or less, at 1.2cm 3 / g or more and 7.0cm 3 / g or less, the apparent density of the porous carbon structure is 0.05g / cm 3 Above and 0.20g / cm 3 The total porosity is in the range of 90% to 99%, and the total porosity is in the range of 80% to 99%.

[0291] Furthermore, it has also been confirmed that the content of (F) in the porous carbon structure of all samples of the porous carbon structures Nos. 1 to 8 and 10 was 0.0002% by mass or less.

[0292] In the samples of the porous carbon structures Nos. 2, 3, 5 to 8, and 10, the pore volume of pores with a diameter of 200 nm or more and 10,000 nm or less was 2.3 cm 3 / g or more and 8.0cm 3 / g or less, and it has been found that the above samples also satisfy the above condition (e).

[0293] Furthermore, it was found that in all samples of the porous carbon structures Nos. 2, 3, 5 to 8, and 10, the pore volume of pores having a diameter of 1 nm or more and 1,000 nm or less satisfied 4.1 cm 3 / g or more and 9.0cm 3 / g range below 4.0cm 3 / g or more and 10.0cm 3 / g or less, and the pore volume of pores with a diameter of 1 nm or more and 200 nm or less satisfies 2.4 cm 3 / g or more and 6.0cm 3 / g range below 2.2cm 3 / g or more and 7.0cm 3 / g or less. It has also been found that the pore volume is larger than those values ​​of Ketjen Black (registered trademark) as a raw material shown in Table 1. In particular, focusing on the pore volume of pores having a diameter of 1 nm or more and 1,000 nm or less, it has been found that the pore volume in each sample of the porous carbon structure Nos. 2, 3, 5 to 8, and 10 is 1.02 times or more of the pore volume of Ketjen Black (registered trademark), and it has been confirmed that the carbonization treatment step is sufficiently performed.

[0294] This can be explained by the fact that PAN (polyacrylonitrile) of the binder and the carbonized product of PAN covering the surface of the Ketjen Black (registered trademark) particles are mostly burned by the oxidation treatment, so that the surface of the Ketjen Black (registered trademark) can be exposed; and in addition, a part of the surface of the Ketjen Black (registered trademark) particles is oxidized and burned. In addition, PAN present at the portion where the Ketjen Black (registered trademark) particles are bonded to each other is not burned because oxygen is difficult to enter, and thus remains in a carbonized form, thereby ensuring the self-supporting ability and strength of the porous carbon structure.

[0295] In comparison, it is understood that in the sample of the porous carbon structure No. 9 oxidized with 5% oxygen, the amount of Ketjen Black (registered trademark) particles oxidized and burned due to the high concentration of oxygen increased more, and as a result, a larger amount of PAN present at the portion where the particles are bonded to each other was burned, and the strength of the porous carbon structure decreased. That is, it is understood that with respect to the sample of the porous carbon structure No. 9, since the carbonization treatment performed in the samples of the porous carbon structures Nos. 1 to 8 and 10 of the present invention was not performed, the self-supporting ability of the porous carbon structure was not obtained.

[0296] On the other hand, in each of the samples of the porous carbon structures No. 1 and No. 4 obtained by carbonization using only nitrogen gas, the pore volume of pores having a diameter of 1 nm or more and 1,000 nm or less and the pore volume of pores having a diameter of 1 nm or more and 200 nm or less became smaller than the pore volume of Ketjen Black (registered trademark) as a raw material. This is because the carbonization product derived from PAN covers the surface of the Ketjen Black (registered trademark) particles.

[0297] It has been confirmed that the porous carbon structures of samples No. 2, 3, 5 to 8 and 10 satisfy the t-curve external specific surface area of ​​900 m 2 / g or more and 1,600m 2 / g or less, within 300m 2 / g or more and 1,600m 2 / g or less.

[0298] [Example 2A: Button Cell (Lithium-Air Battery)]

[0299] In Example 2A, each of the samples of the porous carbon structures No. 1 to 8 and No. 10 of the present invention manufactured (produced) in Example 1A was used as the positive electrode structure 690 ( Figure 6 ) to prepare CR2032 button cell 601( Figure 6 ), and evaluate the battery characteristics of button batteries.

[0300] The porous carbon structure sample No. 9 subjected to oxidation treatment at an oxygen concentration of 5% at a high temperature of 1050° C. was not subjected to battery evaluation as a positive electrode. This is because the porous carbon structure sample No. 9 was not in a state capable of battery evaluation due to its low strength and brittleness.

[0301] A button cell was manufactured as follows. In a dry room (in dry air) with a dew point temperature of -50°C or less, a positive electrode structure obtained by cutting each of the porous carbon structures No. 1 to 8 and No. 10 into a sheet with a diameter (Φ) of 16 mm, a metallic lithium (having a diameter (Φ) of 16 mm and a thickness of 0.2 mm) as a negative electrode structure, and a glass fiber paper (Whatman (registered trademark), GF / A) as a separator impregnated in a 1M-tetraethylene glycol dimethyl ether solution of LiTFS (lithium trifluoromethanesulfonate) as an electrolyte were enclosed in a button cell box (CR2032 type).

[0302] The battery characteristics of each button cell (lithium-air battery) obtained in this way were evaluated in a pure oxygen atmosphere.

[0303] As the battery evaluation conditions, except for 0.4 mA / cm 2 In addition to the current density condition of 0.6 mA / cm 2 and 0.8mA / cm 2 The discharge was performed under the condition of a high current density of , and the time point when the voltage dropped to 2.3 V was taken as the discharge end point, and the discharge capacity per unit weight of the positive electrode was calculated by dividing the obtained discharge capacity by the weight of the porous carbon structure used as the positive electrode.

[0304] For this measurement, a charge / discharge tester (HJ1001SD8, manufactured by HOKUTO DENKO CORPORATION) was used. The results are shown in Table 4.

[0305] [Table 4]

[0306] Table 4. Discharge capacity of air batteries using various porous carbon structures as positive electrodes

[0307]

[0308] According to the results in Tables 2 and 4, it has been shown that, unlike the comparative sample (comparative example) of the porous carbon structure No. 9 which does not satisfy all of the above conditions (a) to (d), all samples of the porous carbon structure No. 1 to 8 and No. 10 of the present invention which satisfy all of the conditions can be used as a self-supporting positive electrode structure in an air battery, and the porous carbon structure can be used alone as a positive electrode material for an air battery without using a current collector such as a metal mesh. It has also been found that the samples as a whole exhibit much higher discharge capacity values ​​than the case where the comparative samples (comparative examples) of the porous carbon structure No. 17 to 22 are used as the positive electrode structure.

[0309] In addition, according to Table 4, it has been found that, compared with the button batteries using each sample of the porous carbon structure No. 1 and No. 4 of the present invention obtained by carbonization with nitrogen only without oxidation treatment as the positive electrode structure, the button batteries using each sample of the porous carbon structure No. 2, 3, 5 to 8 and No. 10 of the present invention obtained by oxidation treatment in an oxidizing gas atmosphere (as the carbonization treatment in the carbonization treatment step (step S4)) as the positive electrode structure not only have a lower charge and discharge rate at 0.4 mA / cm 2 The discharge capacity was higher when the current density was 0.6 mA / cm 2 and 0.8mA / cm 2 It also exhibits higher discharge capacity when discharged at a high current density.

[0310] [Example 1B: Porous Carbon Structure]

[0311] In Example 1B, the preparation of the porous carbon structure samples (porous carbon structures Nos. 11 to 16) and comparative samples (porous carbon structures Nos. 17 to 25) of the present invention, and the properties of the prepared porous carbon structure samples and comparative samples are described.

[0312] (Preparation of Sample No. 11 of the Porous Carbon Structure of the Present Invention)

[0313] First, a mixture slurry was prepared using the following: 65 wt% of porous carbon particles; 10 wt% of carbon fibers; 25 wt% of a bonding polymer material; and a solvent containing N-methylpyrrolidone for uniformly dispersing the above components ( Figure 4 Step S1 in ).

[0314] Here, as the porous carbon particles, carbon black containing 65% by weight of Ketjen Black (registered trademark) was used.

[0315] As the carbon fibers, carbon fibers having an average fiber diameter of 7 μm and an average length of 3 mm were used. As the binder polymer material, polyacrylonitrile (PAN) was used.

[0316] The mixture slurry was formed into a sheet with uniform thickness by a wet film forming method using a doctor blade ( Figure 4 After the mixture slurry is molded, the molded sample is immersed in water (poor solvent) by a non-solvent-induced phase separation method to form the molded sample into a porous film.

[0317] Next, a drying step is performed at 50 to 80° C. for more than 10 hours ( Figure 4 Step S4 in the above method) to remove the volatile solvent from the sample, followed by an infusibility heat treatment at 280°C in air ( Figure 4 Then, as a carbonization step ( Figure 4 After vacuum replacement, the sample was fired at 1000°C for 3 hours in a firing furnace under a nitrogen atmosphere to prepare a porous carbon structure sample ( Figure 4 Step S7 in ).

[0318] Table 2 shows the preparation (manufacturing) conditions of the sample of the porous carbon structure No. 11 of the present invention.

[0319] (Properties of the sample No. 11 of the porous carbon structure of the present invention)

[0320] The characteristics of the sample of the porous carbon structure No. 11 prepared by the above-mentioned steps were examined in the same manner as the measurement of the properties of each sample of the porous carbon structure Nos. 1 to 10, and the results are shown in Table 3.

[0321] Specifically, the sample had a thickness of 510 μm as shown in Table 2, 10.8 mg / cm 2 The basis weight is 646m as shown in Table 3. 2 / g BET specific surface area, as shown in Table 3 540m 2 The sample had a t-curve external specific surface area of ​​1.3477 Å / g, and a total t-curve external specific surface area ratio (SA ratio) of 84% as shown in Table 3. The sample had a porosity of 89.9% as shown in Table 3.

[0322] The secondary scanning electron microscopy images of the porous carbon structure were obtained. Fig.10 Although the porous carbon structure has a sponge-like structure with pores, it exhibits self-supporting strength.

[0323] As shown in Table 3, it has been confirmed that the t-curve external specific surface area of ​​the porous carbon structure sample No. 11 is 540 m 2 / g, which is at 300m 2 / g or more and 1,600m 2 / g or less (the above condition (a)), the pore volume of pores with a diameter of 1 nm or more and 200 nm or less is 1.4 cm 3 / g, which is at 1.2cm 3 / g or more and 7.0cm 3 / g or less (the above condition (b)), the pore volume of pores with a diameter of 1 nm or more and 1,000 nm or less is 2.4 cm 3 / g, which is at 2.3cm 3 / g or more and 10.0cm 3 / g or less (the above condition (c)), and the total porosity is 89.9%, which is in the range of 80% to 99% (the above condition (d)), and the sample satisfies all of the above conditions (a) to (d).

[0324] (Preparation of Sample No. 12 of the Porous Carbon Structure of the Present Invention)

[0325] A sample of porous carbon structure No. 12 was prepared in the same manner as that of porous carbon structure No. 11 except that methanol was used as a poor solvent in the non-solvent-induced phase separation method.

[0326] (Properties of the sample No. 12 of the porous carbon structure of the present invention)

[0327] The characteristics of the sample of the porous carbon structure No. 12 prepared by the above-mentioned steps were examined in the same manner as the measurement of the properties of each sample of the porous carbon structure Nos. 1 to 10, and the results are shown in Table 3.

[0328] Specifically, the sample had a thickness of 470 μm as shown in Table 2, 7.9 mg / cm 2 The basis weight is 646m as shown in Table 3. 2 / g BET specific surface area, as shown in Table 3 533m 2 / g, and a total t-curve external specific surface area ratio (SA ratio) of 83% as shown in Table 3. In addition, the sample had a porosity of 90% as shown in Table 3.

[0329] As shown in Table 3, it has been confirmed that the t-curve external specific surface area of ​​the porous carbon structure sample No. 12 is 533 m 2 / g, which satisfies the above condition (a), and the pore volume of pores with a diameter of 1 nm or more and 200 nm or less is 1.5 cm 3 / g, which satisfies the above condition (b), and the pore volume of pores with a diameter of 1 nm or more and 1,000 nm or less is 2.3 cm 3 / g, which satisfies the above condition (c), and the total porosity is 90.0%, which satisfies the above condition (d), so the sample satisfies all of the above conditions (a) to (d).

[0330] (Preparation of Sample No. 13 of the Porous Carbon Structure of the Present Invention)

[0331] The porous carbon structure sample No. 13 was prepared in the same manner as the porous carbon structure sample No. 11 except that ethanol was used as a poor solvent in the non-solvent-induced phase separation method.

[0332] (Properties of the sample No. 13 of the porous carbon structure of the present invention)

[0333] The characteristics of the sample of the porous carbon structure No. 13 prepared by the above-mentioned steps were examined in the same manner as the measurement of the properties of each sample of the porous carbon structure Nos. 1 to 10, and the results are shown in Table 3.

[0334] Specifically, the sample had a thickness of 542 μm as shown in Table 2, 9.4 mg / cm 2 The basis weight is 709m as shown in Table 3. 2 / g BET specific surface area, as shown in Table 3 567m 2 / g, and a total t-curve external specific surface area ratio (SA ratio) of 80% as shown in Table 3. The sample had a porosity of 91% as shown in Table 3.

[0335] As shown in Table 3, it has been confirmed that the t-curve external specific surface area of ​​the porous carbon structure sample No. 13 is 567 m 2 / g, which satisfies the above condition (a), and the pore volume of pores with a diameter of 1 nm or more and 200 nm or less is 1.5 cm 3 / g, which satisfies the above condition (b), and the pore volume of pores with a diameter of 1 nm or more and 1,000 nm or less is 2.3 cm 3 / g, which satisfies the above condition (c), and the total porosity is 91.0%, which satisfies the above condition (d), so the sample satisfies all of the above conditions (a) to (d).

[0336] (Preparation of each sample of porous carbon structure No. 14 and No. 15 of the present invention)

[0337] Each sample of porous carbon structure No. 14 and No. 15 was prepared in the same manner as the sample of porous carbon structure No. 11 except that: for the sample of porous carbon structure No. 14, a mixture slurry having a composition (mixture composition) of 70 wt% of Ketjen black, 10 wt% of carbon fiber, and 20 wt% of PAN was prepared and used; and for porous carbon structure No. 15, a mixture slurry having a composition (mixture composition) of 85 wt% of Ketjen black, 10 wt% of carbon fiber, and 5 wt% of PAN was prepared and used. Specific preparation (manufacturing) conditions are shown in Table 2.

[0338] (Properties of each sample of the porous carbon structure No. 14 and No. 15 of the present invention)

[0339] The characteristics of each sample of porous carbon structure Nos. 14 and 15 prepared by the above-mentioned steps were examined in the same manner as the measurement of the properties of each sample of porous carbon structure Nos. 1 to 10, and the results are shown in Table 3.

[0340] Specifically, regarding the porous carbon structure No. 14, the sample had a thickness of 220 μm as shown in Table 2, 3.7 mg / cm 2 The basis weight is 931 m as shown in Table 3. 2 / g BET specific surface area, as shown in Table 3 898m 2 / g, and a total t-curve external specific surface area ratio (SA ratio) of 96% as shown in Table 3. In addition, the sample had a porosity of 93% as shown in Table 3.

[0341] Regarding the porous carbon structure No. 15, the sample had a thickness of 245 μm as shown in Table 2, 4.0 mg / cm 2 The basis weight is 1,111 m 2 The BET specific surface area of ​​1,072 m / g is shown in Table 3. 2 / g, and a total t-curve external specific surface area ratio (SA ratio) of 96% as shown in Table 3. In addition, the sample had a porosity of 93% as shown in Table 3.

[0342] As shown in Table 3, it has been confirmed that the t-curve external specific surface area of ​​the porous carbon structure sample No. 14 is 898 m 2 / g, which satisfies the above condition (a), and the pore volume of pores with a diameter of 1 nm or more and 200 nm or less is 2.4 cm 3 / g, which satisfies the above condition (b), and the pore volume of pores with a diameter of 1 nm or more and 1,000 nm or less is 4.0 cm 3 / g, which satisfies the above condition (c), and the total porosity is 92.9%, which satisfies the above condition (d), so the sample satisfies all of the above conditions (a) to (d).

[0343] In addition, as shown in Table 3, it has been confirmed that the t-curve external specific surface area of ​​the porous carbon structure sample No. 15 is 1,072 m 2 / g, which satisfies the above condition (a), and the pore volume of pores with a diameter of 1 nm or more and 200 nm or less is 3.0 cm 3 / g, which satisfies the above condition (b), and the pore volume of pores with a diameter of 1 nm or more and 1,000 nm or less is 4.0 cm 3 / g, which satisfies the above condition (c), and the total porosity is 93.0%, which satisfies the above condition (d), so the sample satisfies all of the above conditions (a) to (d).

[0344] (Preparation of Sample No. 16 of the Porous Carbon Structure of the Present Invention)

[0345] The sample of the porous carbon structure No. 16 was prepared in the same manner as the sample of the porous carbon structure No. 11 except that BLACK PEARLS (registered trademark) 2000 (manufactured by Cabot Corporation) was used as the porous carbon particles; and a mixture slurry having a composition (mixture composition) of 68 wt % BLACK PEARLS (registered trademark), 9 wt % carbon fiber, and 23 wt % PAN was prepared and used. The specific preparation (manufacturing) conditions are shown in Table 2.

[0346] (Properties of the sample No. 16 of the porous carbon structure of the present invention)

[0347] The characteristics of the sample of the porous carbon structure No. 16 prepared by the above-mentioned steps were examined in the same manner as the measurement of the properties of each sample of the porous carbon structure Nos. 1 to 10, and the results are shown in Table 3.

[0348] Specifically, regarding the porous carbon structure No. 16, the sample had a thickness of 170 μm as shown in Table 2, 4.3 mg / cm 2 The basis weight is 930 m as shown in Table 3. 2 / g BET specific surface area, as shown in Table 3 320m 2 / g, and a total t-curve external specific surface area ratio (SA ratio) of 34% as shown in Table 3. In addition, the sample had a porosity of 88% as shown in Table 3.

[0349] As shown in Table 3, it has been confirmed that the t-curve external specific surface area of ​​the porous carbon structure sample No. 16 is 320 m 2 / g, which satisfies the above condition (a), and the pore volume of pores with a diameter of 1 nm or more and 200 nm or less is 2.3 cm 3 / g, which satisfies the above condition (b), and the pore volume of pores with a diameter of 1 nm or more and 1,000 nm or less is 2.8 cm 3 / g, which satisfies the above condition (c), and the total porosity is 88.0%, which satisfies the above condition (d), so the sample satisfies all of the above conditions (a) to (d).

[0350] (Preparation of Sample No. 17 of Porous Carbon Structure as Comparative Sample)

[0351] The sample of the porous carbon structure No. 17 was prepared in the same manner as the sample of the porous carbon structure No. 11, except that a gas diffusion layer sheet made of carbon fiber (TGP-H-060, manufactured by Toray Industries, Inc.) was used as a sheet obtained by molding the mixture slurry into a sheet having a uniform thickness by a wet film-forming method using a doctor blade. The specific preparation (manufacturing) conditions are shown in Table 2.

[0352] (Properties of Sample No. 17 of Porous Carbon Structure as Comparative Sample)

[0353] The characteristics of the sample of the porous carbon structure No. 17 prepared by the above-mentioned steps were examined in the same manner as the measurement of the properties of each sample of the porous carbon structure Nos. 1 to 10, and the results are shown in Table 3.

[0354] Specifically, the sample had a thickness of 190 μm as shown in Table 2, 8.1 mg / cm 2 The basis weight is 80m as shown in Table 3. 2 / g, and as shown in Table 3, the 80 m 2 The sample has a small t-curve external specific surface area of ​​78%.

[0355] As shown in Table 3, it has been confirmed that the sample of the porous carbon structure No. 17 does not satisfy any one of the above conditions (a) to (d), and thus the sample does not satisfy all of the above conditions (a) to (d).

[0356] (Preparation of Sample No. 18 of Porous Carbon Structure as Comparative Sample)

[0357] The sample of the porous carbon structure No. 18 was prepared in the same manner as the sample of the porous carbon structure No. 11, except that an activated carbon fiber woven fabric (CL1420, manufactured by FUTAMURA CHEMICAL CO., LTD.) was used as a sheet obtained by molding the mixture slurry into a sheet having a uniform thickness by a wet film-forming method using a doctor blade. The specific preparation (manufacturing) conditions are shown in Table 2.

[0358] (Properties of Sample No. 18 of Porous Carbon Structure as Comparative Sample)

[0359] The characteristics of the sample of porous carbon structure No. 18 were examined in the same manner as the measurement of the properties of each sample of porous carbon structure Nos. 1 to 10, and the results are shown in Table 3.

[0360] The sample had a thickness of 283 μm as shown in Table 2, 7.9 mg / cm 2 The basis weight is 1,994 m 2 / g, such as the 114 m 2 The results show that the t-curve external specific surface area of ​​2.177 W / g and the total t-curve external specific surface area ratio (SA ratio) of 5.7% are small.

[0361] As shown in Table 3, it has been confirmed that the sample of the porous carbon structure No. 18 does not satisfy all of the above conditions (a) to (d).

[0362] (Preparation of Samples of Porous Carbon Structure Nos. 19 and 20 as Comparative Samples)

[0363] Each sample of porous carbon structure No. 19 and No. 20 was prepared in the same manner as the preparation of porous carbon structure No. 11 except that: for the sample of porous carbon structure No. 19, a mixture slurry having a composition (mixture composition) of 20 wt% of Ketjen black, 10 wt% of carbon fiber, and 70 wt% of PAN was prepared and used; and for porous carbon structure No. 20, a mixture slurry having a composition (mixture composition) of 30 wt% of Ketjen black, 10 wt% of carbon fiber, and 60 wt% of PAN was prepared and used. Specific preparation (manufacturing) conditions are shown in Table 2.

[0364] (Properties of each sample of porous carbon structure No. 19 and No. 20 as comparative samples)

[0365] The characteristics of each sample of porous carbon structure Nos. 19 and 20 prepared by the above-mentioned steps were examined in the same manner as the measurement of the properties of each sample of porous carbon structure Nos. 1 to 10, and the results are shown in Table 3.

[0366] Specifically, regarding the porous carbon structure No. 19, the sample had a thickness of 142 μm as shown in Table 2, and a 2 The basis weight is 34m as shown in Table 3. 2 / g BET specific surface area, as shown in Table 3 22m 2 / g, and a total t-curve external specific surface area ratio (SA ratio) of 65% as shown in Table 3. In addition, the sample has a porosity of 91.4% as shown in Table 3. Therefore, the sample has a small BET specific surface area and a small t-curve external specific surface area.

[0367] Regarding the porous carbon structure No. 20, the sample had a thickness of 170 μm as shown in Table 2, 3.8 mg / cm 2 The basis weight is 79m as shown in Table 3. 2 / g BET specific surface area, as shown in Table 3 39m 2 / g, and a total t-curve external specific surface area ratio (SA ratio) of 49% as shown in Table 3. In addition, the sample had a porosity of 90.1% as shown in Table 3.

[0368] As described above, the porous carbon structures No. 19 and No. 20 each have a small BET specific surface area and a small t-curve external specific surface area.

[0369] As shown in Table 3, it has been confirmed that neither of the samples of the porous carbon structure Nos. 19 and 20 satisfies all of the above conditions (a) to (d).

[0370] (Preparation of Sample No. 21 of Porous Carbon Structure as Comparative Sample)

[0371] The sample of the porous carbon structure No. 21 was prepared in the same manner as the preparation of the porous carbon structure No. 11 except that VULCAN (registered trademark) XC-72 (manufactured by Cabot Corporation) was used as porous carbon particles; and a mixture slurry having a composition (mixture composition) of 68 wt % of VULCAN (registered trademark) XC-72, 9 wt % of carbon fiber, and 23 wt % of PAN was prepared and used. The specific preparation (manufacturing) conditions are shown in Table 2.

[0372] (Properties of Sample No. 21 of Porous Carbon Structure as Comparative Sample)

[0373] The characteristics of the sample of the porous carbon structure No. 21 prepared by the above-mentioned steps were examined in the same manner as the measurement of the properties of each sample of the porous carbon structure Nos. 1 to 10, and the results are shown in Table 3.

[0374] Specifically, regarding the porous carbon structure No. 21, the sample had a thickness of 216 μm as shown in Table 2, and a 2 The basis weight is 153m as shown in Table 3. 2 / g BET specific surface area, as shown in Table 3 66m 2 / g, and a total t-curve external specific surface area ratio (SA ratio) of 43% as shown in Table 3. In addition, the sample had a porosity of 85% as shown in Table 3.

[0375] As shown in Table 3, it has been confirmed that the sample of the porous carbon structure No. 21 does not satisfy all of the above conditions (a) to (d).

[0376] (Preparation of Sample No. 22 of Porous Carbon Structure as Comparative Sample)

[0377] Regarding the sample of the porous carbon structure No. 22, as the composition of the mixture slurry prepared therein (mixture composition), 65 wt% of Ketjen Black (registered trademark) and 35 wt% of PTFE (manufactured by DAIKIN INDUSTRIES, LTD.) as a binder were used, and a solution of the mixture slurry was prepared by dispersing the above components in an aqueous solvent. Here, PTFE means polytetrafluoroethylene.

[0378] Next, an activated carbon fiber woven fabric (CL1420, manufactured by FUTAMURA CHEMICAL CO., LTD.) was used as a supporting material, and on this base film, the above-mentioned water-dispersed mixture slurry was formed into a sheet having a uniform thickness by a wet film-forming method using a doctor blade, thereby preparing a sheet integrated with the activated carbon fiber supporting material.

[0379] Next, the volatile solvent is removed from the prepared sheet, and the sheet is dried to prepare a porous carbon film integrated with the activated carbon fiber woven fabric. The product is used as a porous carbon structure.

[0380] The specific preparation (manufacturing) conditions are shown in Table 2.

[0381] (Properties of Sample No. 22 of Porous Carbon Structure as Comparative Sample)

[0382] The characteristics of the sample of the porous carbon structure No. 22 prepared by the above-mentioned steps were examined in the same manner as the measurement of the properties of each sample of the porous carbon structure Nos. 1 to 10, and the results are shown in Table 3.

[0383] Specifically, regarding the porous carbon structure No. 22, the sample had a thickness of 354 μm as shown in Table 2, and a 2 The basis weight is 1,434 m 2 / g BET specific surface area, as shown in Table 3 291m 2 / g, and a total t-curve external specific surface area ratio (SA ratio) of 20% as shown in Table 3. In addition, the sample had a porosity of 81% as shown in Table 3.

[0384] Regarding the porous carbon structure No. 22, the sample had a thickness of 354 μm as shown in Table 2, 12.6 mg / cm 2 The basis weight is 1,434 m 2 The BET specific surface area of ​​1,142 m / g is shown in Table 3. 2 / g, and a total t-curve external specific surface area ratio (SA ratio) of 20% as shown in Table 3. In addition, the sample had a porosity of 81% as shown in Table 3.

[0385] As shown in Table 3, it has been confirmed that the sample of the porous carbon structure No. 22 does not satisfy all of the above conditions (a) to (d).

[0386] (Preparation of Sample No. 23 of Porous Carbon Structure as Comparative Sample)

[0387] Regarding sample No. 23 porous carbon structure, as the composition of the mixture slurry prepared therein (mixture composition), 90 weight % of Ketjen Black (registered trademark) and 10 weight % of PTFE (manufactured by DAIKIN INDUSTRIES, LTD.) as a binder were used, and a solution of the mixture slurry was prepared by dispersing the above components in ethanol used to prepare the mixture slurry.

[0388] The mixture slurry was formed into a sheet having a uniform thickness by a wet film-forming method using a doctor blade.

[0389] Next, the volatile solvent was removed from the prepared sheet, and the sheet was dried, with the result that the film-like product was broken and no self-supporting film was formed.

[0390] The specific preparation (manufacturing) conditions are shown in Table 2.

[0391] (Properties of Sample No. 23 of Porous Carbon Structure as Comparative Sample)

[0392] Regarding the sample of the porous carbon structure No. 23, since a self-supporting film was not obtained as described above, the characteristics of the sample as shown in Table 3 could not be examined.

[0393] (Preparation of Sample No. 24 of Porous Carbon Structure as Comparative Sample)

[0394] A sample of porous carbon structure No. 24 was prepared in the same manner as porous carbon structure No. 23, except that a molded sheet was prepared by pressing at 10 MPa when forming a sheet from the mixture slurry. The dried film-like product was cracked and did not form a self-supporting film.

[0395] The specific preparation (manufacturing) conditions are shown in Table 2.

[0396] (Properties of Sample No. 24 of the Porous Carbon Structure as Comparative Sample)

[0397] Regarding the sample of the porous carbon structure No. 24, since a self-supporting film was not obtained as described above, the characteristics of the sample as shown in Table 3 could not be examined.

[0398] (Preparation of Sample No. 25 of Porous Carbon Structure as Comparative Sample)

[0399] A sample of porous carbon structure No. 25 was prepared in the same manner as the preparation of porous carbon structure No. 23, except that the composition of the prepared mixture slurry (mixture composition) was 95 wt % of Ketjen Black (registered trademark) and 5 wt % of PTFE (manufactured by DAIKIN INDUSTRIES, LTD.) as a binder. The dried film-like product was broken and a self-supporting film was not formed.

[0400] The specific preparation (manufacturing) conditions are shown in Table 2.

[0401] (Properties of the porous carbon structure sample No. 25 as a comparative sample)

[0402] Regarding the sample of the porous carbon structure No. 25, since a self-supporting film was not obtained as described above, the characteristics of the sample as shown in Table 3 could not be examined.

[0403] [Example 2B: Button Cell (Lithium-Air Cell)]

[0404] In Example 2B, each of the samples of the porous carbon structures No. 11 to No. 16 of the present invention manufactured (produced) in Example 1B was used as the positive electrode structure 690 ( Figure 6 ) to prepare CR2032 button cell 601( Figure 6 ), and the battery characteristics of the button battery were evaluated. For comparison, each comparison sample of the porous carbon structure No. 17 to No. 22 was used as the positive electrode structure 690 ( Figure 6 )A CR2032 type button battery 601 was prepared similarly, and the battery characteristics of the button battery were evaluated.

[0405] When the sample of the porous carbon structure No. 13 of the present invention is used as the positive electrode structure 690, a groove for air flow is formed in the surface of the porous carbon structure. Specifically, as described above, ethanol is used as a poor solvent in the non-solvent-induced phase separation method to prepare the porous carbon structure, and then a groove having a grid pattern is formed in the surface of the porous carbon structure in a wet state to form an air flow path required for an air battery in the surface of the porous carbon structure. The width of the groove as the flow path is about 2 mm, and the depth is about 0.05 mm.

[0406] The battery evaluation was not performed for the comparative samples of the porous carbon structure Nos. 23 to 25. This is because, as described above, these samples did not form a self-supporting film and were not in a state capable of being evaluated for the battery as a positive electrode.

[0407] Similar to the manufacture of the button cell in Example 2A, a button cell was manufactured as follows. In a drying room (in dry air) with a dew point temperature of -50°C or less, the positive electrode structure obtained by cutting each of the porous carbon structures No. 11 to 16 into a sheet with a diameter (Φ) of 16 mm, the metal lithium as the negative electrode structure (whose diameter (Φ) is 16 mm and thickness is 0.2 mm) and the glass fiber paper (Whatman (registered trademark), GF / A) as a separator impregnated in a 1M-tetraethylene glycol dimethyl ether solution of LiTFS (lithium trifluoromethanesulfonate) as an electrolyte were installed in a button cell box (CR2032 type). In this way, an air battery (lithium-air battery) was prepared.

[0408] Regarding the evaluation conditions in the discharge capacity test of the prepared lithium-air battery, the test was conducted at 0.4 mA / cm 2 The discharge current density was carried out, and the time point when the voltage was reduced to 2.3V was taken as the discharge end point, and the discharge capacity per unit weight of the positive electrode (mAh / g) was calculated by dividing the obtained discharge capacity by the weight of the porous carbon structure used as the positive electrode. The test results are shown in Table 4 together with the test results of each button cell (lithium-air battery) manufactured (made) in Example 2A, each of which uses one of the porous carbon structures No. 1 to 8 and No. 10 of the present invention as the positive electrode.

[0409] In addition, similar to the button cell (lithium-air battery) manufactured (produced) in Example 2A, except that 0.4 mA / cm 2 In addition to the discharge current density of 0.6 mA / cm 2 and 0.8mA / cm 2 Some lithium-air batteries manufactured (fabricated) in Example 2B were tested at a higher rate discharge current density of .

[0410] According to the results in Tables 2 and 4, it has been confirmed that, similar to the button cell (lithium-air battery) of Example 2A, unlike the comparative samples (comparative examples) of the porous carbon structure No. 23 to 25 that do not satisfy all of the above conditions (a) to (d), all samples of the porous carbon structure No. 11 to 16 of the present invention that satisfy all of the conditions can be used as a self-supporting positive electrode structure in an air battery, and the porous carbon structure can be used alone as a positive electrode material for an air battery without using a current collector such as a metal mesh. It has also been found that the sample as a whole exhibits a much higher discharge capacity value than when using the comparative samples (comparative examples) of the porous carbon structure No. 17 to 22 that do not satisfy all of the above conditions (a) to (d) as the positive electrode structure.

[0411] As a result, it has been confirmed that according to the air battery using samples of the porous carbon structure Nos. 11 to 16 of the present invention as the positive electrode structure, air is sufficiently supplied to the positive electrode structure 690, so the air battery becomes light in weight and has sufficient output capacity.

[0412] When the comparative sample No. 22 porous carbon structure having an activated carbon fiber woven fabric or the like as a support (which has no self-supporting ability) is used as the positive electrode structure, the 2 The discharge capacity at the discharge current density of 1.3 Å is much smaller than the discharge capacity when using the samples of the self-supporting porous carbon structures Nos. 11 to 16 of the present invention. This result shows the usefulness of the self-supporting porous carbon structure of the present invention.

[0413] In addition, it has been confirmed that when a porous carbon structure (specifically, a No. 19 or 20 porous carbon structure) prepared by a mixture slurry with a low proportion of Ketjen black of porous carbon particles as an active material and not satisfying all of the above conditions (a) to (d) is used as a positive electrode structure, the air battery has a low discharge capacity.

[0414] According to the above, it has been shown that the porous carbon structure of the present invention that satisfies all of the above conditions (a) to (d) does not require a current collector such as a metal mesh and is used alone as a positive electrode material for an air battery. It has also been shown that an air battery using the above porous carbon structure has high battery capacity and high load characteristics, which are caused by high air or oxygen diffusivity, high ion transport efficiency and wide reaction field caused by the porous carbon structure.

[0415] Industrial Applicability

[0416] As described above, the porous carbon structure of the present invention is a porous carbon structure with an unprecedented high pore volume. Using the porous carbon structure as the positive electrode of the air battery can provide an air battery with high battery capacity and high load characteristics, and the high battery capacity and high load characteristics are produced by high air or oxygen diffusivity, high ion transmission efficiency and wide reaction field caused by the porous carbon structure. In addition, because the porous carbon structure has a self-supporting ability, the porous carbon structure can be used alone as a positive electrode material without using a current collector such as a metal mesh, so it is possible to provide a small size and light weight and an air battery suitable for increasing capacity. Therefore, it is expected that the present invention is preferably used for air batteries expected to have a significant increase in demand in the future.

[0417] Reference numerals list

[0418] 10 Image of the skeleton of the porous carbon structure of the present invention

[0419] 11 Image of pores having a diameter of 1 nm or more and 1,000 nm or less in the porous carbon structure of the present invention

[0420] 12 Image of pores having a diameter of 200 nm or more and 10,000 nm or less in the porous carbon structure of the present invention

[0421] 13 Image of carbon fiber of porous carbon structure of the present invention

[0422] 100,610 negative electrode structure

[0423] 500 Air Battery

[0424] 510, 620, 621 positive electrode structure

[0425] 520 negative current collector electrode

[0426] 525 Positive current collector electrode

[0427] 540, 660 Diaphragm

[0428] 600, 601 button battery

[0429] 630 Button Battery Type Restraint Tool

[0430] 635 Current collector

[0431] 640 Metal Layer

[0432] 650 Spacer

[0433] 670 space (space for filling electrolyte)

[0434] 680 Metal Mesh

[0435] 690 Porous Carbon Structure

Claims

1. A porous carbon structure for an air battery cathode, the porous carbon structure comprising pores and a carbon-containing skeleton, and satisfying all of the following conditions (a) to (e): (a) t-curve external specific surface area at 900m 2 / g or more and 1,600m 2 / g or less; (b) The pore volume of pores with a diameter of 1 nm or more and 200 nm or less, measured by the BJH method at 2.2 cm 3 / g or more and 7.0cm 3 / g or less; (c) The pore volume of pores with a diameter of 1 nm or more and 1,000 nm or less, measured by the BJH method at 4.0 cm 3 / g or more and 10.0cm 3 / g or less; (d) a total porosity in the range of 92% or more and 99% or less; and (e) The pore volume of pores with a diameter of 200 nm or more and 10,000 nm or less, measured by mercury intrusion porosimetry at 2.3 cm 3 / g or more and 8.0cm 3 / g or less.

2. The porous carbon structure according to claim 1, wherein the pore volume of the pores with a diameter of 1 nm or more and 200 nm or less in (b) is measured by the BJH method at a depth of more than 2.4 cm 3 / g and 6.0cm 3 / g or less.

3. The porous carbon structure according to claim 1, wherein the pore volume of the pores having a diameter of 1 nm or more and 1,000 nm or less in (c) is measured by the BJH method at 4.1 cm 3 / g or more and 9.0cm 3 / g or less.

4. The porous carbon structure according to any one of claims 1 to 3, wherein the apparent density of the porous carbon structure is 0.05 g / cm 3 Above and 0.20g / cm 3 Within the following range. 5 . The porous carbon structure according to claim 1 , wherein the skeleton is made of carbon.

6. A method for producing a porous carbon structure according to any one of claims 1 to 5, the method comprising the following steps: preparing a mixture slurry containing porous carbon particles and a binding polymer material; forming the mixture slurry; immersing the sample obtained by the molding step in a solvent in which the solubility of the bonding polymer material is low; drying the sample obtained by the immersion step; and The sample obtained through the drying step is subjected to a carbonization treatment, wherein the carbonization treatment is performed in an atmosphere of an oxidizing gas. 7 . The method according to claim 6 , wherein the oxygen concentration of the oxidizing gas is in the range of greater than 0.03% and less than 5%. 8 . The method according to claim 6 , wherein the carbonization treatment is performed at a treatment temperature in the range of 350° C. or higher and 3000° C. or lower.

9. The method according to claim 6 or 7, wherein the carbonization treatment is performed until the pore volume of pores having a diameter of 1 nm or more and 1,000 nm or less in the product obtained by the carbonization treatment reaches 1.02 times or more the pore volume in the porous carbon particles.

10. The method according to claim 6 or 7, wherein the mixture slurry further contains carbon fibers.

11. The method according to claim 6 or 7, further comprising, after the drying step and before the carbonization step, performing an infusibility treatment on the sample obtained by the drying step.

12. The method according to claim 6 or 7, further comprising: After the carbonization treatment, the sample obtained by the carbonization treatment is subjected to another carbonization treatment under an inert gas atmosphere. 13 . A positive electrode material for an air battery, the positive electrode material comprising the porous carbon structure according to claim 1 . 14 . An air battery comprising a positive electrode structure, a negative electrode structure, a separator, and an electrolyte member, wherein the positive electrode structure comprises the porous carbon structure according to claim 1 . 15 . The air battery according to claim 14 , wherein the porous carbon structure has a flow path through which air or oxygen passes. 16 . The air battery according to claim 14 , wherein the positive electrode structure comprises a metal-containing positive electrode substrate having a flow path through which air or oxygen passes, and wherein the metal-containing positive electrode substrate is in electrical contact with the porous carbon structure.

Citation Information

Patent Citations

  • Lithium air battery and using method thereof

    JP2018133168A

  • Porous carbon and metal-air battery

    JP2015076125A

  • Carbon-based cathode for lithium-air battery and preparation method thereof

    KR1020120105736A